Aqueous polymer latexes suitable as film-forming copolymers for use as binders in aqueous coating compositions

By using specific ethylenically unsaturated monomers in polymer latex for aqueous emulsion polymerization, the problems of unbalanced performance of polymer dispersions and fossil carbon dependence in the prior art are solved, and polymers with high stability and good performance are achieved Latex, suitable for water-based coatings and other applications.

CN116134056BActive Publication Date: 2025-02-25BASF SE
View PDF 63 Cites 0 Cited by

Patent Information

Application Number
CN202180060254.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-07-19
Publication Date
2025-02-25
Estimated Expiration
2041-07-19

AI Technical Summary

Technical Problem

Existing polymer dispersions have balanced challenges in providing hardness and resistance to adhesion, while their stability and performance are difficult to balance in different applications, and monomers based on fossil origins lead to dependence on fossil carbon.

Method used

Polymer latex with good balanced application profiles were prepared by polymerization using aqueous emulsions containing ethylenically unsaturated monomers such as isobutyl acrylate, 2-methylbutyl acrylate and isoamyl acrylate. The latex contains at least 90% by weight of the designated monomer in the polymer component and some of the monomers are obtained from biological sources, reducing the need for fossil carbon.

Benefits of technology

The stability and balance properties of polymer latex in aqueous coating compositions are achieved, including improved flexibility, adhesion resistance, weather resistance and whitening resistance, while reducing the amount of fossil carbon used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004113746240000351
    Figure BDA0004113746240000351
  • Figure BDA0004113746240000352
    Figure BDA0004113746240000352
  • Figure BDA0004113746240000353
    Figure BDA0004113746240000353
Patent Text Reader

Abstract

The present invention relates to an aqueous polymer latex which is suitable as a film-forming copolymer of a binder in an aqueous coating composition and which can be obtained by aqueous emulsion polymerization of an ethylenically unsaturated monomer M, wherein the ethylenically unsaturated monomer M comprises: based on the total amount of the monomers M, 20 to 95% by weight of at least one monomer M1 selected from isobutyl acrylate and isoamyl acrylate and mixtures thereof; based on the total amount of the monomers M, 0 to 55% by weight of at least one monomer M2 selected from ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-amyl acrylate, C6-C 20 C5-C ‑alkyl esters and methacrylic acid 20 ‑alkyl esters and mixtures thereof; based on the total amount of monomer M, 5 to 50% by weight of at least one monomer M3, the monomer M3 being selected from tert-butyl acrylate, C1‑C4‑alkyl methacrylate, C5‑C 20 -Cycloalkyl esters, C5-C 20 ‑Cycloalkyl esters, acrylic acid, C5‑C 20 ‑Cycloalkyl methyl esters, C5‑C methacrylate 20 cycloalkylmethyl esters, wherein in the above monomers the cycloalkyl group is monocyclic, bicyclic or tricyclic, and wherein 1 or 2 CH2 moieties of the cycloalkyl group may be replaced by O, and wherein the cycloalkyl group may be unsubstituted or carry 1, 2, 3 or 4 methyl groups, and monovinylaromatic monomers and mixtures thereof; based on the total amount of the monomers M, 0.05 to 4% by weight of at least one monomer M4, the monomer M4 being selected from monoethylenically unsaturated monomers having an acidic group; wherein the total amount of the monomers M1 and M2 is in the range of 45 to 95% by weight, in particular 50 to 90% by weight, especially 55 to 85% by weight, based on the total amount of the ethylenically unsaturated monomers M, wherein the total amount of the monomers M1, M2 and M3 is at least 90% by weight, in particular at least 95% by weight, based on the total amount of the ethylenically unsaturated monomers M.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to aqueous polymer latexes of film-forming copolymers obtainable by aqueous emulsion polymerization of ethylenically unsaturated monomers M, said ethylenically unsaturated monomers M comprising at least 90% by weight, based on the monomers M, of at least two different nonionic monomers selected from acrylate monomers, methacrylate monomers and monovinylaromatic monomers. The invention also relates to a process for the preparation of such polymer latexes and to the use of these polymer latexes as binders in aqueous coating compositions, in particular latex paints, especially latex paints for architectural coatings and wood coatings, such as wood lacquers and wood stains.

[0002] Polymer latexes, also known as polymer dispersions, are well known, in particular as binders or binder components, also known as co-binders, for use in coating compositions. One of the important requirements for a binder or co-binder in a coating composition is that it provides hardness and blocking resistance to the coating. Further, the polymer latex should provide low water absorption, good weather resistance, in particular resistance to moisture and UV radiation, and good coating flexibility.

[0003] US 4,267,091 describes a binder composition for lacquers and pebble plasters containing:

[0004] A) a polymer latex obtained by emulsion polymerization of ethylenically unsaturated monomers containing an alkyl (meth)acrylate as a main monomer component and a monomer containing a carbonyl group such as formylstyrene and diacetone acrylamide,

[0005] B) Bisacylhydrazide compounds

[0006] C) Water soluble salts: zinc salts.

[0007] WO 2011 / 009874 describes aqueous polymer dispersions based on ethylenically unsaturated monomers which contain 20 to 75% by weight of tert-butyl (meth)acrylate. The polymer latexes offer improved flame retardancy and are therefore particularly suitable for producing architectural coatings, thermal insulation coatings and construction adhesives.

[0008] WO 2012 / 130712 describes polymer latexes prepared by two-step emulsion polymerization and their use as binders in aqueous coating compositions for wood coatings. The polymer dispersions exhibit good storage stability and the coating compositions prepared therefrom give coatings having good wet adhesion and good hardness.

[0009] WO 2014 / 07595 describes the use of a polymer latex comprising at least two different monomers, the homopolymers of which have a theoretical glass transition temperature of at least 25°C and at least two different monomers, the homopolymers of which have a theoretical glass transition temperature below 25°C as a binder for improving the color retention of exterior coatings.

[0010] WO 2016 / 042116 describes a polymer dispersion obtained by two-step emulsion polymerization in the presence of a polymerizable emulsifier and its use as a binder in an aqueous coating composition for wood coatings. The coating composition prepared therefrom gives a coating having good water resistance and good hardness.

[0011] Despite progress in many areas, providing polymer dispersions with a balanced application profile remains a challenging task, as not only application properties but also the stability of the polymer dispersion must be considered. In particular, it is difficult to simultaneously reconcile the performance requirements of different coatings through the binder. Often, attempts to improve one property of a coating by changes in the polymer composition of the binder result in significant deterioration of other properties of the coating.

[0012] Although the polymer dispersions described in the above references have unique advantages in one or more aspects, they do not always have a well-balanced application profile. In addition, they are based solely on monomers prepared from fossil sources. In view of the ongoing discussion on the impact of CO2 emissions, there is a need to reduce fossil carbon in the production of polymer latexes.

[0013] It was therefore an object of the present invention to provide polymer latexes with a well-balanced application profile, which makes it possible to use the polymer latexes as binders or co-binders in aqueous coating compositions, in particular aqueous coating compositions for exterior applications. However, the fossil carbon requirement should also be reduced.

[0014] Surprisingly, it has been found that polymer latexes based on acrylate monomers, methacrylate monomers and / or monovinyl aromatic monomers and mixtures thereof containing a certain amount of monomer M1 selected from isobutyl acrylate and isoamyl acrylate improve the coating properties of coating compositions, in particular the whitening resistance, water absorption and flexibility of the coating composition, i.e. the coating, without deteriorating other properties, such as anti-blocking and surface hardness. In addition, the monomer M1 can be obtained - at least its alkanol part - from a biological source, thereby allowing for the need to reduce fossil carbon in the production of polymer latexes.

[0015] The present invention therefore relates to aqueous polymer latexes of film-forming copolymers obtainable by aqueous emulsion polymerization of ethylenically unsaturated monomers M comprising:

[0016] 20 to 90% by weight, in particular 25 to 90% by weight, especially 30 to 85% by weight, based on the total amount of monomers M, of at least one monomer M1 selected from isobutyl acrylate, 2-methylbutyl acrylate and isoamyl acrylate and mixtures thereof;

[0017] 0 to 55% by weight, for example 5 to 55%, in particular 0 to 50% by weight or 5 to 50% by weight, especially 0 to 40% by weight or 5 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-pentyl acrylate, C6-C 20 -alkyl esters and C5-C 20 - alkyl esters and mixtures thereof;

[0018] - 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, C1-C4-alkyl methacrylates, C5-C4-alkyl acrylic acid esters 20 -Cycloalkyl esters, C5-C 20 -Cycloalkyl esters, acrylic acid C5-C 20 -Cycloalkyl methyl ester, C5-C 20 - cycloalkyl methyl esters - wherein the cycloalkyl group in the above monomers is monocyclic, bicyclic or tricyclic and wherein 1 or 2 CH2 moieties of the cycloalkyl group may be replaced by O and wherein the cycloalkyl group may be unsubstituted or carry 1, 2, 3 or 4 methyl groups - and monovinyl aromatic monomers and mixtures thereof;

[0019] 0.05 to 4% by weight, preferably 0.05 to 3.5% by weight, in particular 0.1 to 4% by weight or 0.1 to 3% by weight, especially 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monomers having an acidic group,

[0020] % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M.

[0021] The present invention also relates to a method for preparing the aqueous polymer latex of the present invention. The method comprises performing aqueous emulsion polymerization of the monomer M.

[0022] The invention also relates to the use of these polymer latexes as binders or co-binders in aqueous coating compositions, in particular in aqueous compositions for wood coatings such as aqueous wood stain formulations, aqueous wood lacquer formulations and aqueous varnish formulations for wood surfaces, and for aqueous architectural coatings. The invention also relates to the use of the aqueous polymer latexes described herein to increase the resistance to water or humidity of a coating obtained from an aqueous coating composition described herein.

[0023] Furthermore, the present invention relates to an aqueous coating composition comprising:

[0024] a) a binder polymer in the form of an aqueous polymer latex as defined herein; and

[0025] b) at least one other ingredient which is conventionally used in aqueous coating compositions and which is not a binder.

[0026] The present invention has several advantages.

[0027] - The polymer latex is stable and provides a good and balanced application profile for aqueous coating compositions.

[0028] Since the polymer latexes contain considerable amounts of monomers M1 obtainable from biological sources, they make possible a significant reduction in the fossil carbon requirement, in particular a reduction of at least 10%, in particular at least 15% or even at least 20%.

[0029] - Aqueous coating compositions containing the polymer latex of the present invention as a binder or co-binder have improved flexibility.

[0030] - Aqueous coating compositions containing the polymer latex of the present invention as binder or co-binder exhibit very good anti-blocking properties.

[0031] Aqueous coating compositions containing the polymer latex of the invention as binder or co-binder have good weather resistance, especially resistance to moisture and UV radiation, and in particular have improved resistance to whitening.

[0032] - Aqueous coating compositions containing the polymer latex of the present invention exhibit improved scrub resistance, improved gloss and improved thickening efficiency, reduced dirt pickup and comparable opacity, adhesion and stain resistance at high and low shear rates.

[0033] Due to their balanced application profile, polymer latexes are very useful as binders or co-binders in waterborne wood coatings and have beneficial properties in both waterborne primer and waterborne topcoat formulations.

[0034] Here and throughout the application, the term "(meth)acryloyl" includes both acryloyl and methacryloyl groups. Thus, the term "(meth)acrylate" includes both acrylate and methacrylate, and the term "(meth)acrylamide" includes both acrylamide and methacrylamide.

[0035] As used herein and throughout this application, the term "aqueous coating composition" means a liquid aqueous coating composition that contains water as a continuous phase in an amount sufficient to achieve flowability.

[0036] Here and throughout the application, the terms "wt.-%" and "% by weight (% bw)" are used synonymously.

[0037] Here and throughout the application, the term "pphm" means parts by weight per 100 parts of monomers, corresponding to a relative amount of % by weight of a certain substance based on the total amount of monomers M.

[0038] Here and throughout the application, the term "ethylenically unsaturated monomer" is understood to mean a monomer having at least one C=C double bond, for example 1, 2, 3 or 4 C=C double bonds, which are free-radically polymerizable, i.e. polymerized under the conditions of an aqueous free-radical emulsion polymerization process to obtain a polymer having a main chain of carbon atoms. Here and throughout the application, the term "monoethylenically unsaturated" is understood to mean a monomer having a single C=C double bond, which is susceptible to free-radical polymerization under the conditions of an aqueous free-radical emulsion polymerization process.

[0039] Here and throughout the application, the terms "ethoxylated" and "polyethoxylated" are used synonymously to refer to compounds having oligomeric or polyoxyethylene groups formed by repeating units O-CH2CH2. In this context, the term "degree of ethoxylation" relates to the average number of repeating units O-CH2CH2 in these compounds.

[0040] Here and throughout the application, the term "nonionic" in the context of compounds, especially monomers, means that the respective compound does not carry any ionic functional groups or any functional groups which can be converted into ionic groups by protonation or deprotonation.

[0041] Here and throughout the specification, the prefix C used in conjunction with a chemical compound or a molecular moiety is n -C m The term "C1-C n "Alkyl" refers to a linear or branched saturated hydrocarbon radical having 1 to n carbon atoms. n / C m The term "alkyl" refers to a mixture of two alkyl groups, one of which has n carbon atoms and the other has m carbon atoms.

[0042] For example, the term C1-C 20 Alkyl refers to a linear or branched saturated hydrocarbon radical having 1 to 20 carbon atoms, while C1-C4 alkyl refers to a linear or branched saturated hydrocarbon radical having 1 to 4 carbon atoms, C5-C 20Alkyl refers to a linear or branched saturated hydrocarbon radical having 5 to 20 carbon atoms. Examples of alkyl include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, 2-methylpropyl (isopropyl), 1,1-dimethylethyl (tert-butyl), pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 2,2-dimethylpropyl, 1-ethylpropyl, hexyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 3,3-dimethylbutyl, 1-ethylbutyl, 2-ethylbutyl, 1,1,2-trimethylpropyl, 1,2,2-trimethylpropyl, 1-ethyl-1-methylpropyl, 1-ethyl-2-methylpropyl, n-heptyl, 2-heptyl, n-octyl, 2-octyl, 2-ethylhexyl, nonyl, isononyl, decyl, undecyl, dodecyl, tridecyl, isotridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, heneicosyl and in the case of nonyl, isononyl, decyl, undecyl, dodecyl, tridecyl, isotridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, heneicosyl and their isomers, in particular mixtures of isomers such as "isononyl" and "isodecyl". Examples of C1-C4-alkyl are methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 2-methylpropyl or 1,1-dimethylethyl.

[0043] The term "C5-C 20 "-cycloalkyl" refers to a monocyclic or bicyclic alicyclic group which is unsubstituted or substituted with 1, 2, 3 or 4 methyl groups, wherein the C5-C 20 The total number of carbon atoms in the cycloalkyl group is from 5 to 20. 20- Examples of cycloalkyl groups include, but are not limited to, cyclopentyl, cyclohexyl, methylcyclohexyl, dimethylcyclohexyl, cycloheptyl, cyclooctyl, cyclododecyl, cyclohexadecyl, norbornyl (=bicyclo[2.2.1]heptyl) and isobornyl (=1,7,7-trimethylbicyclo[2.2.1]heptyl). In cycloalkyl groups, one or two CH2 groups may be replaced by non-adjacent oxygen ring atoms to produce heterocycloaliphatic groups. Such groups include, but are not limited to, tetrahydrofuran-2-yl, tetrahydrofuran-3-yl, tetrahydropyran-2-yl, tetrahydropyran-3-yl, tetrahydropyran-4-yl, 1,3-dioxolan-2-yl, 1,3-dioxolan-4-yl, 2,2-dimethyl-1,3-dioxolan-4-yl, 1,4-dioxan-2-yl, 1,3-dioxan-2-yl, 1,3-dioxan-4-yl, 1,3-dioxan-5-yl, 2,2-dimethyl-1,3-dioxan-4-yl, 2,2-dimethyl-1,3-dioxan-5-yl.

[0044] The term "C5-C 20 "-cycloalkylmethyl" refers to a C5-C6- 20 - a cycloalkyl group.

[0045] According to the invention, the monomer M comprises at least one monomer M1 selected from isobutyl acrylate, 2-methylbutyl acrylate and isoamyl acrylate and mixtures thereof. Isoamyl acrylate is also referred to as isopentyl acrylate or 3-methylbutyl acrylate, respectively. 2-Methylbutyl acrylate is a chiral compound and can therefore exist in racemic form or in the form of a non-racemic mixture containing one of its enantiomers in excess. According to the invention, the monomer M1 comprises non-racemic 2-methylbutyl acrylate and racemic 2-methylbutyl acrylate.

[0046] In a specific embodiment group, the monomer M1 comprises at least 50% by weight, in particular at least 80% by weight, especially at least 90% by weight of isobutyl acrylate, based on the total amount of monomer M1. In particular, the monomer M1 is isobutyl acrylate.

[0047] In a further specific embodiment group, the monomer M1 comprises at least 50 wt %, in particular at least 80 wt %, especially at least 90 wt %, of isoamyl acrylate, based on the total amount of monomer M1. In this specific embodiment group, the monomer M1 is in particular isoamyl acrylate.

[0048] In a further specific embodiment group, the monomer M1 comprises at least 50% by weight, in particular at least 80% by weight, of 2-methylbutyl acrylate, based on the total amount of monomer M1. In this specific embodiment group, the monomer M1 is especially 2-methylbutyl acrylate.

[0049] In another specific embodiment group, the monomer M1 is a mixture comprising at least 50% by weight, in particular at least 80% by weight of isoamyl acrylate and 2-methylbutyl acrylate, based on the total amount of monomer M1, and optionally up to 50% by weight, in particular not more than 20% by weight, of isobutyl acrylate, based on the total amount of monomer M1. In this specific embodiment group, the monomer molar ratio of 3-methylbutyl acrylate to 2-methylbutyl acrylate is in particular in the range of 1:1 to 10:1.

[0050] Isobutyl acrylate, 2-methylbutyl acrylate and isoamyl acrylate are typically prepared by the esterification reaction of acrylic acid with isobutyl alcohol (2-methyl-1-propanol), 2-methylbutanol or isoamyl alcohol (3-methyl-1-butanol), respectively, or by the transesterification reaction of methyl acrylate or ethyl acrylate with isobutyl alcohol (2-methyl-1-propanol), 2-methyl-1-butanol or isoamyl alcohol (3-methyl-1-butanol), respectively.

[0051] Isobutanol, 2-methylbutanol and isopentanol and mixtures thereof can be produced on a large scale by fermentation of biological sources or renewable raw materials, respectively, through a variety of renewable raw materials, including corn, wheat, sorghum, barley and sugar cane, especially raw materials containing cellulose. Therefore, the addition of monomer M1 to the polymer latex significantly increases the amount of biochar in the polymer latex, thereby reducing the demand for fossil carbon, thereby reducing the demand for CO2 produced by the polymer latex. In particular, fermentation can produce a mixture containing different alkanols, in which isobutanol, 2-methyl-1-butanol and 3-methyl-1-butanol can be separated by conventional techniques such as fractionation. Therefore, either pure alcohols (purity>90%) can be obtained, or a total amount of at least 80%, in particular at least 90%, containing at least two selected from the group comprising isobutanol, 2-methyl-1-butanol and 3-methyl-1-butanol can be obtained. For example, a mixture comprising at least 80% by weight of 2-methylbutanol and 3-methylbutanol and up to 20% by weight of isobutanol can be used for the esterification or transesterification reaction. In this mixture, the molar ratio of 3-methylbutanol to 2-methyl-1-butanol can vary, for example from 1:10 to 10:1, in particular in the range of 1:1 to 10:1.

[0052] The acrylic acid used for the esterification reaction can be obtained from fossil sources according to standard procedures. Acrylic acid can also be prepared from renewable raw materials, for example according to WO 2006 / 092272 or DE 10 2006 039 203 A or EP 2 922 580.

[0053] It is also possible that at least a portion of the analytes are used for the synthesis of bio-based monomers M1 from renewable raw materials according to the mass balance method. Accordingly, in addition to fossil feedstocks, renewable feedstocks such as bio-naphtha (as described in EP 2 290 045 A1 or EP 2 290 034 A1) enter a chemical production system, such as a steam cracker. The renewable feedstocks are converted along the chemical value chain into products such as acrylic acid, isobutanol, isopentanol or 2-methylbutanol, or isobutyl acrylate, isopentanyl acrylate or 2-methylbutyl acrylate. The content of renewable materials in these products is determined by the mass balance method and can be allocated to these products.

[0054] Therefore, a specific embodiment of the present invention relates to a polymer latex as defined herein, wherein the carbon atoms of the isobutyl group, 2-methylbutanol group and isopentyl group in the monomer M1 are at least biologically derived, i.e., they are at least partially composed of biochar. In particular, the isobutyl alcohol, 2-methyl-1-butanol and isopentyl alcohol used to produce the monomer M1 preferably have a biochar content of at least 90 mol% based on the total amount of carbon atoms of isobutyl alcohol, 2-methylpentanol and isopentyl alcohol, respectively. This content is advantageously higher, in particular greater than or equal to 95 mol%, preferably greater than or equal to 98 mol%, advantageously equal to 100 mol%. Similarly, acrylic acid can be produced from renewable materials. However, acrylic acid produced from biomaterials has not been available on a large scale so far. Therefore, the monomer M1 has a biochar content of preferably at least 51 mol%, particularly at least 54 mol%, especially at least 57 mol%, based on the total amount of carbon atoms of isobutyl acrylate, 2-methylbutyl acrylate and isopentyl acrylate, respectively. By using monomers M1 of at least partial biological origin, the demand for fossil carbon in the polymer latex can be significantly reduced. In particular, an amount of carbon of biological origin of at least 10 mol %, in particular at least 15 mol % or at least 20 mol % or more, such as 30 mol % or 40 mol % or more can be achieved.

[0055] The term "biochar" means that the carbon is of biological origin, coming from biological material / renewable resources. The content of biochar and the content of biomaterial are expressions indicating the same value. A material of renewable origin or biomaterial is an organic material in which the carbon comes from carbon dioxide that has been recently fixed (on a human scale) from the atmosphere by photosynthesis. Biomaterial (100% carbon of natural origin) has a carbon content greater than 10 -12 The isotope ratio 14 C / 12 C, usually about 1.2×10 -12 , while fossil materials have a zero ratio. In fact, isotopes 14 C is formed in the atmosphere and then integrated through photosynthesis on time scales of at most several decades.14 The half-life of C is 5730 years. Therefore, materials from photosynthesis, that is, plants in general, must have isotopes 14 The maximum content of C. The content of biomass or the content of biochar can be determined according to standards ASTM D 6866-12, method B (ASTM D 6866-06) and ASTM D 7026 (ASTM D 7026-04).

[0056] The monomers M of the latex-forming polymer may comprise, in addition to the monomers M1, one or more monomers M2 as defined above.

[0057] Suitable monomers M2 are selected from the group consisting of:

[0058] - n-ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-pentyl acrylate;

[0059] -Acrylic acid C6-C 20 -alkyl esters, including but not limited to n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, n-decyl acrylate, isodecyl acrylate, 2-propylheptyl acrylate, lauryl acrylate, C acrylate 12 / C 14 -Alkyl esters, acrylic acid C 12 -C 15 -alkyl esters, isotridecyl acrylate, acrylic acid C 16 / C 18 - alkyl esters and octadecyl acrylate;

[0060] -Methacrylic acid C5-C 20 - alkyl esters, including but not limited to n-pentyl methacrylate, n-hexyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, n-decyl methacrylate, 2-propylheptyl methacrylate, lauryl methacrylate, C methacrylate 12 / C 14 -Alkyl esters, methacrylate C 12 -C 15 -alkyl esters, isotridecyl methacrylate, C methacrylate 16 / C 18 - alkyl esters and octadecyl methacrylate;

[0061] - and mixtures thereof.

[0062] Preferred monomers M2 are selected from the group consisting of n-ethyl acrylate, n-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, 2-propylheptyl acrylate and mixtures thereof, for example a mixture of n-butyl acrylate and 2-ethylhexyl acrylate or a mixture of n-butyl acrylate and ethyl acrylate or a mixture of ethyl acrylate, n-butyl acrylate and 2-ethylhexyl acrylate, and mixtures thereof.

[0063] More preferred monomers M2 are selected from the group consisting of n-butyl acrylate and 2-ethylhexyl acrylate and mixtures thereof.

[0064] Suitable monomers M3 are selected from the group consisting of:

[0065] - C1-C4-alkyl methacrylic acid esters, for example methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, isobutyl methacrylate and tert-butyl methacrylate;

[0066] - tert-butyl acrylate;

[0067] -(meth)acrylic acid C5-C 20 - Cycloalkyl esters, including but not limited to cyclohexyl acrylate, cyclohexyl methacrylate, norbornyl acrylate, norbornyl methacrylate, isobornyl acrylate, isobornyl acrylate, 1,3-dioxan-5-yl-acrylate, 1,3-dioxan-5-yl-methacrylate, 2,2-dimethyl-1,3-dioxan-5-yl-acrylate, 2,2-dimethyl-1,3-dioxan-5-yl-methacrylate;

[0068] -(meth)acrylic acid C5-C 20 - Cycloalkyl methyl esters, including but not limited to cyclohexyl methacrylate, cyclohexyl methyl methacrylate, 1,3-dioxolan-4-yl methyl acrylate, 1,3-dioxolan-4-yl methyl methacrylate, 2,2-dimethyl-1,3-dioxolan-4-yl methyl acrylate, 2,2-dimethyl-1,3-dioxolan-4-yl methyl methacrylate, tetrahydrofuran-2-yl-methyl acrylate (tetrahydrofuran acrylate) and tetrahydrofuran-2-yl methyl methacrylate (tetrahydrofuran methacrylate);

[0069] - monovinyl aromatic monomers, such as styrene, 2-methylstyrene, 4-methylstyrene;

[0070] and mixtures thereof.

[0071] Preferred monomers M3 are selected from the group consisting of:

[0072] - C1-C4-alkyl methacrylic acid esters, in particular methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate and tert-butyl methacrylate;

[0073] - tert-butyl acrylate;

[0074] - Cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate;

[0075] - styrene;

[0076] and mixtures thereof.

[0077] Particularly mentioned monomers M3 are selected from the group consisting of:

[0078] -Methyl methacrylate, n-butyl methacrylate;

[0079] - tert-butyl acrylate;

[0080] - Cyclohexyl methacrylate, isobornyl methacrylate;

[0081] - styrene;

[0082] and mixtures thereof.

[0083] In particular, the monomers M3 comprise methyl methacrylate in an amount of at least 50% by weight, in particular at least 80% by weight or 100% by weight, based on the total amount of monomers M3 in the monomers M. More particularly, the monomers M3 are selected from the group consisting of methyl methacrylate and combinations of methyl methacrylate with n-butyl methacrylate, tert-butyl acrylate, cyclohexyl methacrylate, isobornyl methacrylate or with styrene.

[0084] Suitable monomers M4 include but are not limited to

[0085] - monoethylenically unsaturated monocarboxylic acids having 3 to 6 carbon atoms, for example acrylic acid, methacrylic acid, crotonic acid, 2-ethylacrylic acid, 2-propylacrylic acid, 2-acryloyloxyacetic acid and 2-methacryloyloxyacetic acid;

[0086] - monoethylenically unsaturated dicarboxylic acids having 4 to 6 carbon atoms, such as itaconic acid, citraconic acid and fumaric acid;

[0087] - half esters of monoethylenically unsaturated dicarboxylic acids having 4 to 6 carbon atoms with C1-C4-alkanols, for example methanol or ethanol, for example half esters of itaconic acid, citraconic acid, maleic acid or fumaric acid with methanol or ethanol;

[0088] - monoethylenically unsaturated sulfonic acids such as vinylsulfonic acid, allylsulfonic acid, styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid,

[0089] - monoethylenically unsaturated phosphonic acids such as vinylphosphonic acid, allylphosphonic acid, styrylphosphonic acid and 2-acrylamido-2-methylpropanephosphonic acid,

[0090] - monoethylenically unsaturated phosphoric acids, for example the monophosphates of hydroxyalkyl acrylates, the monophosphates of hydroxyalkyl methacrylates, the monophosphates of alkoxylated hydroxyalkyl acrylates and the monophosphates of alkoxylated hydroxyalkyl methacrylates, in particular the monophosphates of hydroxyethyl acrylate, hydroxypropyl acrylate or hydroxybutyl acrylate and the monophosphates of hydroxyethyl methacrylate, hydroxypropyl methacrylate or hydroxybutyl methacrylate, and the monophosphates of ethoxylated hydroxy-C2-C4-alkyl acrylates and the monophosphates of propoxylated hydroxy-C2-C4-alkyl acrylates and the monophosphates of ethoxylated hydroxy-C2-C4-alkyl methacrylates and the monophosphates of propoxylated hydroxy-C2-C4-alkyl methacrylates.

[0091] The above-mentioned monomers M4 can be present in their acidic form or in the form of their salts, in particular in the form of their alkali metal salts or ammonium salts.

[0092] Among the above-mentioned monomers M4, monoethylenically unsaturated monocarboxylic acids and monoethylenically unsaturated dicarboxylic acids are preferred. Acrylic acid, methacrylic acid, itaconic acid and mixtures thereof are particularly preferred. Monoethylenically unsaturated monocarboxylic acids are more preferred, in particular acrylic acid, methacrylic acid and mixtures thereof. In a specific embodiment group, the monomer M4 comprises methacrylic acid. In particular, the monomer M4 is methacrylic acid or a mixture of acrylic acid and methacrylic acid.

[0093] The total amount of monomers M4 is 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, especially 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M.

[0094] Preferably, monomer M comprises:

[0095] 20 to 90% by weight, in particular 25 to 90% by weight, especially 30 to 85% by weight, based on the total amount of monomers M, of monomers M1 having at least 50 mol % of biochar;

[0096] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-ethyl acrylate, n-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, 2-propylheptyl acrylate and mixtures thereof, for example a mixture of n-butyl acrylate with 2-ethylhexyl acrylate or a mixture of n-butyl acrylate with ethyl acrylate or a mixture of ethyl acrylate with n-butyl acrylate and 2-ethylhexyl acrylate, and mixtures thereof;

[0097] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0098] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monocarboxylic acids and monoethylenically unsaturated dicarboxylic acids and mixtures thereof,

[0099] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, in particular 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 5 ...9 wt % or 55 to 94.8 wt % or 55 to 94.8 wt %, in

[0100] In particular, the monomer M comprises:

[0101] 20 to 90% by weight, in particular 25 to 90% by weight, especially 30 to 85% by weight, based on the total amount of monomers M, of monomers M1 having at least 50 mol % of biochar;

[0102] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0103] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, methyl methacrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0104] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monocarboxylic acids;

[0105] % or 55 to 94.5 wt %, in particular 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, and the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M.

[0106] Even more preferably, the monomer M comprises:

[0107] 20 to 90% by weight, in particular 25 to 90% by weight, especially 30 to 85% by weight, based on the total amount of monomers M, of monomers M1 having at least 50 mol % of biochar;

[0108] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0109] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of a monomer M3 selected from methyl methacrylate and a combination of methyl methacrylate with at least one further monomer M3 selected from tert-butyl acrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene;

[0110] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, especially 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from acrylic acid, methacrylic acid, itaconic acid and mixtures thereof,

[0111] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, especially 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, wherein the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M.

[0112] In particular, monomer M comprises:

[0113] 20 to 90% by weight, in particular 25 to 90% by weight, especially 30 to 85% by weight, based on the total amount of monomers M, of monomers M1 having at least 50 mol % of biochar;

[0114] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0115] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, of methyl methacrylate as monomer M3, based on the total amount of the monomers M;

[0116] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from methacrylic acid and mixtures of acrylic acid and methacrylic acid,

[0117] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, especially 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, and in particular the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M.

[0118] In a specific embodiment group 1, the monomer M comprises:

[0119] 20 to 90% by weight, in particular 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar, as monomer M1;

[0120] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-ethyl acrylate, n-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, 2-propylheptyl acrylate and mixtures thereof, for example a mixture of n-butyl acrylate with 2-ethylhexyl acrylate or a mixture of n-butyl acrylate with ethyl acrylate or a mixture of ethyl acrylate with n-butyl acrylate and 2-ethylhexyl acrylate and mixtures thereof;

[0121] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0122] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monocarboxylic acids and monoethylenically unsaturated dicarboxylic acids and mixtures thereof,

[0123] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, in particular 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, and in particular the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 92 wt %, especially at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M.

[0124] In a particular group 1 of embodiments, the monomer M preferably comprises:

[0125] 20 to 90% by weight, in particular 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar, as monomer M1;

[0126] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0127] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, methyl methacrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0128] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monocarboxylic acids;

[0129] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, especially 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, and in particular 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, and in particular the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M (embodiment group 1a).

[0130] In a particular group 1 of embodiments, the monomer M more preferably comprises:

[0131] 20 to 90% by weight, in particular 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar, as monomer M1;

[0132] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0133] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, based on the total amount of monomers M, of a monomer M3 selected from methyl methacrylate and a combination of methyl methacrylate with at least one further monomer M3 selected from tert-butyl acrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene;

[0134] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, especially 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from acrylic acid, methacrylic acid, itaconic acid and mixtures thereof,

[0135] % or 55 to 94.5 wt %, in particular 50 to 89.95 wt % or 50 to 94.9 wt % or 50 to 94.8 wt % or 50 to 94.5 wt %, especially 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, and in particular 55 to 84.95 wt % or 55 to 94.9 wt % or 55 to 94.8 wt % or 55 to 94.5 wt %, based on the total amount of the ethylenically unsaturated monomers M, and in particular the total amount of the monomers M1, M2 and M3 is at least 90 wt %, in particular at least 95 wt %, based on the total amount of the ethylenically unsaturated monomers M (embodiment group 1b).

[0136] In specific embodiment group 1, the monomer M comprises in particular:

[0137] 20 to 90% by weight, in particular 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar, as monomer M1;

[0138] 0 to 55% by weight, in particular 0 to 50% by weight, especially 0 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 chosen from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures of n-butyl acrylate and 2-ethylhexyl acrylate;

[0139] 5 to 50% by weight, in particular 10 to 45% by weight, especially 15 to 45% by weight, of methyl methacrylate as monomer M3, based on the total amount of the monomers M;

[0140] 0.05 to 4% by weight or 0.1 to 4% by weight, preferably 0.05 to 3.5% by weight, particularly 0.1 to 3% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total weight of the monomers M, of at least one monomer M4 selected from methacrylic acid and mixtures of acrylic acid and methacrylic acid,

[0141] The total amount of monomers M1 and M2 is 45 to 94.95% by weight or 45 to 94.9% by weight or 45 to 94.8% by weight or 45 to 94.5% by weight, based on the total amount of ethylenically unsaturated monomers M, in particular 50 to 89.95% by weight or 50 to 94.9% by weight or 50 to 94.8% by weight or 50 to 94.5% by weight, especially 55 to 84.95% by weight or 55 to 94.9% by weight or 55 to 94.8% by weight or 55 to 94.5% by weight, and the total amount of monomers M1, M2 and M3 is at least 90% by weight, in particular at least 95% by weight, based on the total amount of ethylenically unsaturated monomers M (embodiment group 1c).

[0142] In specific embodiment group 2, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in specific embodiment group 1.

[0143] In specific embodiment group 2, embodiment 2a is preferred, wherein the types and amounts of monomers M1, M2, M3 and M4 are as defined in specific embodiment group 1a, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0144] In specific embodiment group 2, embodiment 2b is particularly preferred, wherein the types and amounts of monomers M1, M2, M3 and M4 are as defined in the more preferred embodiment group 1b, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0145] In specific embodiment group 2, embodiment 2c is particularly preferred, in which the types and amounts of monomers M1, M2, M3 and M4 are as defined in special embodiment group 1c, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0146] In specific embodiment group 3, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate based on the total amount of monomer M1 instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in specific embodiment group 1.

[0147] In specific embodiment group 3, preferred embodiment 3a, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate based on the total amount of monomer M1 instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in specific embodiment group 1a.

[0148] In specific embodiment group 3, embodiment 3b is particularly preferred, wherein, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate based on the total amount of monomer M1 instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in the more preferred embodiment group 1b.

[0149] In specific embodiment group 3, embodiment 3c is particularly preferred, in which, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate, based on the total amount of monomer M1, instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in special embodiment group 1c.

[0150] In addition to the above-mentioned monomers M1, M2, M3 and M4, the monomer M may further include one or more other monomers different from the above-mentioned monomers M. Suitable monomers M different from the monomers M1, M2, M3 and M4 include but are not limited to

[0151] - monomers M5 selected from monoethylenically unsaturated nonionic monomers having a solubility of at least 60 g / L in deionized water at 20° C. and 1 bar;

[0152] - monomers M6 selected from monoethylenically unsaturated nonionic monomers having silane functions or epoxy groups;

[0153] - monomers M7 selected from polyethylenically unsaturated monomers, ie monomers having at least two non-conjugated ethylenically unsaturated double bonds;

[0154] - Monomers M8 selected from monoethylenically unsaturated copolymerizable UV initiators.

[0155] Suitable nonionic monoethylenically unsaturated monomers M5 are, for example, those which have radicals selected from hydroxyalkyl groups, in particular hydroxy-C2-C4-alkyl groups, primary carboxamide groups, urea groups and keto groups.

[0156] The total amount of monomers M5 generally does not exceed 10% by weight, in particular 7% by weight, based on the total amount of monomers M. In particular, the total amount of monomers M5 (if present) is typically 0.05 to 10% by weight, in particular 0.1 to 7% by weight, especially 0.1 to 5% by weight or 0.1 to 4% by weight or 0.5 to 3% by weight or 1 to 3% by weight, based on the total weight of monomers M.

[0157] Examples of monomers M5 having carboxamide groups (hereinafter referred to as monomers M5a) include, but are not limited to, primary amides of monoethylenically unsaturated monocarboxylic acids having 3 to 6 carbon atoms, such as acrylamide and methacrylamide, and C1-C4-alkaneamides of monoethylenically unsaturated monocarboxylic acids having 3 to 6 carbon atoms, such as N-methylacrylamide, N-ethylacrylamide, N-propylacrylamide, N-isopropylacrylamide, N-butylacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-propylmethacrylamide, N-methylisopropylacrylamide and N-butylmethacrylamide. Most preferably, monomer M5a is selected from acrylamide and methacrylamide.

[0158] Examples of monomers M5 having urea groups (hereinafter referred to as monomers M5b) are C1-C4-alkyl esters of acrylic acid or methacrylic acid and N-C1-C4-alkylamides of acrylic acid or methacrylic acid, wherein the C1-C4-alkyl group carries a urea group or a 2-oxoimidazolinyl group, such as 2-(2-oxo-imidazolin-1-yl)ethyl acrylate, 2-(2-oxo-imidazolin-1-yl)ethyl methacrylate (also referred to as 2-ureidoacrylate and 2-ureidoacrylate, respectively). The invention also includes urea, urea methacrylate, N-(2-acryloyloxyethyl) urea, N-(2-methacryloyloxyethyl) urea, N-(2-(2-oxo-imidazolin-1-yl) ethyl) acrylamide, N(2(2-oxy-imidazolin-1-yl) ethyl) methacrylamide, and allyl or vinyl substituted urea and allyl or vinyl substituted 2-oxoimidazolin compounds, such as 1-allyl-2-oxoimidazolin, N-allyl urea and N-vinyl urea.

[0159] Examples of monomer M5 having a keto group (hereinafter referred to as monomer M5c) are

[0160] - C2-C8-oxyalkyl esters of acrylic acid or methacrylic acid and N-C2-C8-oxyalkyl amides of acrylic acid or methacrylic acid, for example diacetone acrylamide (DAAM) and diacetone methacrylamide, and

[0161] - C1-C4-alkyl esters of acrylic acid or methacrylic acid and N-C1-C4-alkylamides of acrylic acid or methacrylic acid, in which the C1-C4-alkyl group carries a 2-acetoacetoxy group (also known as acetoacetoxy group) of the formula OC(═O)—CH2—C(═O)—CH3, for example acetoacetoxyethyl acrylate, acetoacetoxypropyl methacrylate, acetoacetoxybutyl methacrylate and 2-(acetoacetoxy)ethyl methacrylate.

[0162] Suitable monomers M6 include monoethylenically unsaturated silane-functional monomers (monomers M6a), for example, carrying at least one mono-, di- and / or tri-C1-C4-alkoxysilane group in addition to the ethylenically unsaturated double bond, such as vinyl trimethoxysilane, vinyl triethoxysilane, methacryloxyethyl trimethoxysilane, methacryloxyethyl triethoxysilane and mixtures thereof. The amount of silane-functional monomers M6a (if present) generally does not exceed 1 pphm and is generally in the range of 0.01 to 1 pphm.

[0163] Suitable monomers M6 also include monoethylenically unsaturated monomers with at least one epoxy group (monomers M6b), in particular glycidyl groups such as glycidyl acrylate, glycidyl methacrylate, 2-oxyethyl glycidyl acrylate and 2-oxyethyl glycidyl methacrylate. The amount of monomer M6b (if present) generally does not exceed 2 phm and is generally in the range of 0.01 to 2 phm.

[0164] The monomers M may also contain polyethylenically unsaturated monomers (monomers M7), ie monomers having at least two non-conjugated ethylenically unsaturated double bonds. The amount of the monomers M7 is usually not more than 1 pphm.

[0165] Examples of polyethylenically unsaturated monomers M7 include:

[0166] - diesters of monoethylenically unsaturated C3-C6-monocarboxylic acids with saturated aliphatic or cycloaliphatic diols, in particular diesters of acrylic acid or methacrylic acid, for example diacrylates and dimethacrylates of ethylene glycol (1,2-ethanediol), propylene glycol (1,2-propylene glycol), 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol (2,2-dimethyl-1,3-propanediol), 1,6-hexanediol and 1,2-cyclohexanediol;

[0167] - monoesters of monoethylenically unsaturated C3-C6 monocarboxylic acids with monoethylenically unsaturated aliphatic or alicyclic monohydroxy compounds, such as acrylic and methacrylic esters of vinyl alcohol (vinyl alcohol), allyl alcohol (2-propen-1-ol), 2-cyclohexen-1-ol or norbornyl alcohol, such as allyl acrylate and allyl methacrylate; and

[0168] -Divinyl aromatic compounds, such as 1,3-divinylbenzene, 1,4-divinylbenzene.

[0169] The polymerized monoethylenically unsaturated copolymerizable UV initiator M8 leads to crosslinking of the polymer chain under sunlight. The monomer M8 carries an ethylenically unsaturated double bond, in particular an acrylate or methacrylate group and a portion that is decomposed by ultraviolet radiation to form free radicals. Such groups are typically benzophenone groups, acetophenone groups, benzoyl alcohol groups or carbonate groups attached to a benzene ring. These compounds are disclosed in, for example, EP 346734, EP 377199, DE 4037079, DE3844444, EP 1213 and US2015 / 0152297. Examples include, but are not limited to, 4-acryloxybenzophenone (=4-benzoylphenyl acrylate), 4-methacryloxybenzophenone (=4-benzoylphenyl-2-methyl acrylate), 4-(2-acryloxyethoxy)benzophenone (=2-(4-benzoylphenoxy)ethyl acrylate), 4-(2-methacryloxyethoxy)benzophenone (=2-(4-benzoylphenoxy)ethyl-2-methyl acrylate), O-(2-(meth)acryloxyethyl)-O-(benzoylphenyl)carbonate and O-(2-(meth)acryloxyethyl)-O-(acetylphenyl)carbonate. The amount of the monomer M7 will generally not exceed 1 pphm, and if present, is generally present in an amount of 0.01 to 1 pphm, especially in an amount of 0.02 to 0.5 pphm.

[0170] In particular, the monomers M include at least one monomer M4 and at least one monomer M5.

[0171] In particular, the monomer M consists of:

[0172] 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar as monomer M1;

[0173] 0 to 50% by weight, for example 5 to 50% by weight, in particular 0 to 40% by weight or 5 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from n-ethyl acrylate, n-butyl acrylate, n-pentyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, 2-propylheptyl acrylate and mixtures thereof, for example a mixture of n-butyl acrylate and 2-ethylhexyl acrylate or a mixture of n-butyl acrylate and ethyl acrylate or a mixture of ethyl acrylate and n-butyl acrylate and 2-ethylhexyl acrylate and mixtures thereof;

[0174] 10 to 45% by weight, in particular 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0175] 0.05 to 4% by weight or 0.1 to 4% by weight, in particular 0.05 to 3.5% by weight or 0.1 to 3.5% by weight or 0.1 to 3% by weight or 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total amount of the monomers M, of one or more monoethylenically unsaturated monomers M4;

[0176] 0 to 9.95% by weight, in particular 0.1 to 7% by weight or 0.1 to 5% by weight, based on the total weight of the monomers M, of one or more nonionic monomers M5;

[0177] 0 to 1% by weight, in particular 0 to 0.5% by weight, of one or more monomers M7;

[0178] The total amount of monomers M1 and M2 is in the range of 50 to 89.95% by weight or 50 to 89.85% by weight or 50 to 89.8% by weight or 50 to 89.7% by weight or 50 to 89.4% by weight, especially 55 to 84.95% by weight or 55 to 84.85% by weight or 55 to 84.8% by weight or 55 to 84.7% by weight or 55 to 84.4% by weight, based on the total amount of ethylenically unsaturated monomers M, and the total amount of monomers M1, M2 and M3 is at least 90% by weight, especially at least 94.4% by weight or at least 94.7% by weight or at least 94.8% by weight or at least 94.9% by weight, based on the total amount of ethylenically unsaturated monomers M (embodiment group 4).

[0179] More particularly, the monomer M comprises:

[0180] 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar as monomer M1;

[0181] 0 to 50% by weight, for example 5 to 50% by weight, in particular 0 to 40% by weight or 5 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from n-butyl acrylate and 2-ethylhexyl acrylate and a mixture of n-butyl acrylate and 2-ethylhexyl acrylate;

[0182] 10 to 45% by weight, in particular 15 to 45% by weight, based on the total amount of monomers M, of at least one monomer M3 selected from tert-butyl acrylate, n-butyl methacrylate, methyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene and mixtures thereof;

[0183] 0.05 to 4% by weight or 0.1 to 4% by weight, in particular 0.05 to 3.5% by weight or 0.1 to 3.5% by weight or 0.1 to 3% by weight or 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total amount of the monomers M, of one or more monoethylenically unsaturated monomers M4;

[0184] 0 to 9.95% by weight, in particular 0.1 to 7% by weight or 0.1 to 5% by weight, based on the total weight of the monomers M, of one or more nonionic monomers M5;

[0185] 0 to 1% by weight, in particular 0 to 0.5% by weight, of one or more monomers M7;

[0186] % or 55 to 84.4 wt. %, based on the total amount of the ethylenically unsaturated monomers M; and wherein the total amount of the monomers M1, M2 and M3 is in the range of 50 to 89.95 wt. % or 50 to 89.85 wt. % or 50 to 89.8 wt. % or 50 to 89.7 wt. % or 50 to 89.4 wt. %, in particular 55 to 84.95 wt. % or 55 to 84.85 wt. % or 55 to 84.8 wt. % or 55 to 84.7 wt. % or 55 to 84.4 wt. %, based on the total amount of the ethylenically unsaturated monomers M (at least 90 wt. %, in particular at least 94.4 wt. % or at least 94.7 wt. % or at least 94.8 wt. % or at least 94.9 wt. % of embodiment group 4a).

[0187] Even more preferably, the monomer M comprises:

[0188] 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar as monomer M1;

[0189] 0 to 50% by weight, for example 5 to 50% by weight, in particular 0 to 40% by weight or 5 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from n-butyl acrylate and 2-ethylhexyl acrylate and a mixture of n-butyl acrylate and 2-ethylhexyl acrylate;

[0190] 10 to 45% by weight, in particular 15 to 45% by weight, based on the total amount of monomers M, of a monomer M3 selected from methyl methacrylate and a combination of methyl methacrylate with at least one further monomer M3 selected from tert-butyl acrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene;

[0191] 0.05 to 4% by weight or 0.1 to 4% by weight, in particular 0.05 to 3.5% by weight or 0.1 to 3.5% by weight or 0.1 to 3% by weight or 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total amount of the monomers M, of one or more monoethylenically unsaturated monomers M4;

[0192] 0 to 9.95% by weight, in particular 0.1 to 7% by weight or 0.1 to 5% by weight, based on the total weight of the monomers M, of one or more nonionic monomers M5;

[0193] 0 to 1% by weight, in particular 0 to 0.5% by weight, of one or more monomers M7;

[0194] The total amount of monomers M1 and M2 is in the range of 50 to 89.95% by weight or 50 to 89.85% by weight or 50 to 89.8% by weight or 50 to 89.7% by weight or 50 to 89.4% by weight, especially 55 to 84.95% by weight or 55 to 84.85% by weight or 55 to 84.8% by weight or 55 to 84.7% by weight or 55 to 84.4% by weight, based on the total amount of ethylenically unsaturated monomers M, and the total amount of monomers M1, M2 and M3 is at least 90% by weight, especially at least 94.4% by weight or at least 94.7% by weight or at least 94.8% by weight or at least 94.9% by weight, based on the total amount of ethylenically unsaturated monomers M (embodiment group 4b).

[0195] In particular, monomer M comprises:

[0196] 25 to 90% by weight, in particular 30 to 85% by weight, based on the total amount of monomers M, of isobutyl acrylate, in particular isobutyl acrylate with at least 50 mol % of biochar as monomer M1;

[0197] 0 to 50% by weight, for example 5 to 50% by weight, in particular 0 to 40% by weight or 5 to 40% by weight, based on the total amount of monomers M, of at least one monomer M2 selected from n-butyl acrylate and 2-ethylhexyl acrylate and a mixture of n-butyl acrylate and 2-ethylhexyl acrylate;

[0198] 10 to 45% by weight, in particular 15 to 45% by weight, of methyl methacrylate as monomer M3, based on the total amount of the monomers M;

[0199] 0.05 to 4% by weight or 0.1 to 4% by weight, in particular 0.05 to 3.5% by weight or 0.1 to 3.5% by weight or 0.1 to 3% by weight or 0.2 to 3% by weight or 0.5 to 3% by weight or 0.5 to 2% by weight, based on the total amount of the monomers M, of one or more monoethylenically unsaturated monomers M4;

[0200] 0 to 9.95% by weight, in particular 0.1 to 7% by weight or 0.1 to 5% by weight, based on the total weight of the monomers M, of one or more nonionic monomers M5;

[0201] 0 to 1% by weight, in particular 0 to 0.5% by weight, of one or more monomers M7;

[0202] The total amount of monomers M1 and M2 is in the range of 50 to 89.95% by weight or 50 to 89.85% by weight or 50 to 89.8% by weight or 50 to 89.7% by weight or 50 to 89.4% by weight, especially 55 to 84.95% by weight or 55 to 84.85% by weight or 55 to 84.8% by weight or 55 to 84.7% by weight or 55 to 84.4% by weight, based on the total amount of ethylenically unsaturated monomers M, and the total amount of monomers M1, M2 and M3 is at least 90% by weight, especially at least 94.4% by weight or at least 94.7% by weight or at least 94.8% by weight or at least 94.9% by weight, based on the total amount of ethylenically unsaturated monomers M (embodiment group 4c).

[0203] In specific embodiment group 5, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3 and M4 are as defined in specific embodiment group 4.

[0204] In specific embodiment group 5, embodiment 5a is preferred, wherein the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in specific embodiment group 4a, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0205] In specific embodiment group 5, embodiment 5b is particularly preferred, in which the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in specific embodiment group 4b, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0206] In specific embodiment group 5, embodiment 5c is particularly preferred, in which the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in specific embodiment group 4c, except that monomer M1 is isoamyl acrylate instead of isobutyl acrylate.

[0207] In specific embodiment group 6, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate based on the total amount of monomer M1 instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in specific embodiment group 4.

[0208] In specific embodiment group 6, preferred embodiment 6a, wherein the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in specific embodiment group 4a, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate, based on the total amount of monomer M1, instead of isobutyl acrylate.

[0209] In specific embodiment group 6, embodiment 6b is particularly preferred, wherein, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate based on the total amount of monomer M1 instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in the more preferred embodiment group 4b.

[0210] In specific embodiment group 6, embodiment 6c is particularly preferred, in which, except that monomer M1 is a mixture of at least 80% by weight of isoamyl acrylate and butyl 2-methacrylate and optionally up to 20% of isobutyl acrylate, based on the total amount of monomer M1, instead of isobutyl acrylate, the types and amounts of monomers M1, M2, M3, M4 and M5 are as defined in special embodiment group 4c.

[0211] Another group 7 of embodiments relates to the polymer latex of the present invention, wherein the monomer M comprises or consists of:

[0212] a) 50 to 70% by weight, based on the total weight of the monomers M, of isobutyl acrylate as monomer M1,

[0213] b) 30 to 50% by weight, based on the total weight of the monomers M, of methyl methacrylate as monomer M3,

[0214] c) 0.1 to 4% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight, especially 0.5 to 2% by weight, based on the total weight of the monomers M, of one or more monomers M4 selected from the group consisting of monoethylenically unsaturated carboxylic acids,

[0215] d) 0 to 5% by weight, in particular 0.1 to 4% by weight, preferably 0.2 to 3% by weight or 0.5 to 3% by weight, very preferably 1 to 3% by weight, based on the total weight of the monomers M, of one or more monoethylenically unsaturated carboxylic acid amides as monomers M5,

[0216] e) 0 to 10% by weight of one or more other ethylenically unsaturated nonionic monomers different from the monomers M1, methyl methacrylate, M4 and M5, preferably selected from the monomers M2 and M3 different from methyl methacrylate, for example selected from tert-butyl acrylate, n-butyl acrylate, n-pentyl acrylate, C6-C 10 -alkyl esters, in particular 2-propylheptyl acrylate, n-octyl acrylate, 2-octyl acrylate, 2-ethylhexyl acrylate, C2-C 10 - Alkyl esters, in particular 2-ethylhexyl methacrylate, butyl methacrylate and tert-butyl methacrylate, and vinyl aromatic monomers, in particular styrene.

[0217] In embodiment group 7, isobutyl acrylate (IBA) and methyl methacrylate (MMA) account for at least 95% by weight of the monomer composition M. For example, isobutyl acrylate may be present in an amount of 55 to 65% by weight of the monomer M, and methyl methacrylate may be present in an amount of 35 to 45% by weight of the monomer M.

[0218] In the preferred embodiment group 7 of subgroup 7a, the monomer composition M comprises the following

[0219] a) 50 to 69.8% by weight, in particular 55 to 64.8% by weight, of isobutyl acrylate,

[0220] b) 30 to 49.8% by weight, in particular 35 to 44.8% by weight, of methyl methacrylate,

[0221] c) 0.1 to 4% by weight, in particular 0.2 to 3% by weight or 0.5 to 3% by weight and especially 0.5 to 2% by weight of monoethylenically unsaturated carboxylic acids,

[0222] d) 0.1 to 4% by weight, preferably 0.2 to 3% by weight or 0.5 to 3% by weight, even more preferably 1 to 3% by weight, of a monoethylenically unsaturated carboxylic acid amide,

[0223] The % by weight values ​​refer to the total weight of the monomers M.

[0224] In a particularly preferred embodiment, subgroup 7b of group 7, the monomer composition M consists of

[0225] a) 50 to 69.6% by weight, in particular 55 to 64.6% by weight or 55 to 64% by weight, of isobutyl acrylate,

[0226] b) 30 to 49.6% by weight, in particular 35 to 44.6% by weight or 35 to 44% by weight, of methyl methacrylate,

[0227] c) 0.2 to 3% by weight, in particular 0.5 to 3% by weight, especially 0.5 to 2% by weight, of a monoethylenically unsaturated carboxylic acid selected from acrylic acid, methacrylic acid and itaconic acid,

[0228] d) 0.2 to 3% by weight, in particular 0.5 to 3% by weight, especially 0.5 to 2% by weight, of a monoethylenically unsaturated carboxylic acid amide selected from acrylamide and methacrylamide,

[0229] The % by weight values ​​refer to the total weight of the monomers M.

[0230] For example, in subgroup 7b of the embodiment, the monomer composition M consists of

[0231] a) 50 to 69% by weight, in particular 55 to 64% by weight, of isobutyl acrylate,

[0232] b) 30 to 49% by weight, in particular 35 to 44% by weight, of methyl methacrylate,

[0233] c) 0.5 to 3% by weight, in particular 0.5 to 2% by weight, of acrylic acid,

[0234] d) 0.5 to 3% by weight, in particular 0.5 to 2% by weight, of acrylamide

[0235] The % by weight values ​​refer to the total weight of the monomers M.

[0236] For example, in subgroup 7b of the embodiment, the monomer composition M consists of

[0237] a) 50 to 69% by weight, in particular 55 to 64% by weight, of isobutyl acrylate,

[0238] b) 30 to 49% by weight, in particular 35 to 44% by weight, of methyl methacrylate,

[0239] c) 0.5 to 3% by weight, in particular 0.5 to 2% by weight, of methacrylic acid,

[0240] d) 0.5 to 3% by weight, in particular 0.5 to 2% by weight, of acrylamide.

[0241] In a preferred embodiment of embodiment group 7, at least part of the isobutyl acrylate of component a) has been produced from renewable raw materials, i.e. at least part of the isobutyl acrylate of component a) is bio-based isobutyl acrylate, which has been partially or completely obtained from renewable raw materials. In addition, isobutyl acrylate obtained from fossil raw materials and isobutyl acrylate that has been partially or completely obtained from renewable raw materials can be used.

[0242] Preferably, the particles of the copolymer contained in the polymer latex have a Z average particle size, determined by QELS, in the range of 30-500 nm, in particular in the range of 40-450 nm. The particle size distribution of the copolymer particles contained in the polymer latex can be unimodal or almost unimodal, which means that the distribution function of the particle size has a single maximum and no specific shoulder. The particle size distribution of the copolymer particles contained in the polymer latex can also be multimodal or almost multimodal, which means that the distribution function of the particle size has at least two different maxima or at least one maximum and at least one distinct shoulder.

[0243] If not otherwise specified, the size of the particles and the distribution of particle size are determined by quasielastic light scattering (QELS), also known as dynamic light scattering (DLS). The measurement method is described in ISO 13321:1996 standard. It can be measured using a high-performance particle sizer (HPPS). For this reason, the aqueous polymer latex sample is diluted and the dilution is analyzed. In the context of QELS, the aqueous dilution can have a polymer concentration in the range of 0.001 to 0.5 weight %, depending on the particle size. For most cases, a suitable concentration is 0.01 weight %. However, higher or lower concentrations can be used to achieve the best signal-to-noise ratio. Dilution can be achieved by adding the polymer latex to an aqueous solution of water or a surfactant to avoid flocculation. Generally, by using 0.1 weight % of a nonionic emulsifier (e.g., ethoxylated C 16 / C 18 An aqueous solution of alkanol (ethoxylation degree 18) was used as diluent. Measurement configuration: HPPS from Malvern, automated, equipped with continuous flow cuvette and Gilson autosampler. Parameters: measurement temperature 20.0°C; measurement time 120 seconds (6 cycles of 20 seconds each); scattering angle 173°; wavelength laser 633 nm (HeNe); medium refractive index 1.332 (aqueous); viscosity 0.9546 mPa·s. The measurement gives the average value (fitted average) of the second-order cumulant analysis, i.e. the Z-average value. The "fitted average" is the average, intensity-weighted hydrodynamic particle size on the nm scale.

[0244] The hydrodynamic particle size can also be determined by hydrodynamic chromatography (HDC) fractionation, as described, for example, by H. Wiese, "Characterization of Aqueous Polymer Dispersions", Polymer Dispersions and Their Industrial Applications (Wiley-VCH Journal, 2002), pages 41-73. For further details, reference is made to the following examples and descriptions.

[0245] In a specific group of embodiments, the copolymer particles contained in the polymer latex have a Z average particle size, measured by QELS, in the range of 30 to 200 nm, in particular in the range of 40 to 150 nm. In a particular group of embodiments, the particle size distribution of the copolymer particles contained in the polymer latex is in particular unimodal or almost unimodal, which means that the distribution function of the particle size has a single maximum.

[0246] In another specific group of embodiments, the copolymer particles contained in the polymer latex have a Z average particle size in the range of 150 to 500 nm, in particular in the range of 200 to 400 nm, as determined by QELS. In this particular group of embodiments, the particle size distribution of the copolymer particles contained in the polymer latex is particularly multimodal, in particular bimodal, meaning that the distribution function of the particle size has at least two maxima. Generally, the particle size distribution of the polymer particles in the polymer dispersion obtained by the method described herein as determined by QELS has a first maximum in the range of 30 to 150 nm and a second maximum in the range of 200 to 500 nm. Preferably, the first maximum is in the range of 50 to 130 nm and the second maximum is in the range of 200 to 400 nm.

[0247] If the polymer particles contain different copolymers which differ in their monomer composition, the copolymers contained in the polymer particles may form a single phase or also different phases. Preferably, the polymer particles contained in the aqueous polymer latex of the present invention comprise at least one polymer phase, wherein the polymer has a glass transition temperature Tg of not more than 40° C., in particular at most 25° C., for example in the range of -25 to +40° C., in particular in the range of -20 to +25° C.

[0248] The glass transition temperature referred to herein is the actual glass transition temperature. The actual glass transition temperature can be experimentally determined by differential scanning calorimetry (DSC) according to ISO 11357-2:2013, preferably with sample preparation according to ISO 16805:2003.

[0249] According to a particularly preferred embodiment group of the present invention, the polymer particles contained in the aqueous polymer latex of the present invention include a polymer phase (1) and a polymer phase (2), wherein the polymer phase (1) has a glass transition temperature Tg(1) in the range of -25 to +40°C, in particular in the range of -20 to +20°C, and the polymer phase (2) has a glass transition temperature Tg(2) in the range of +50 to +150°C, in particular in the range of +60 to +120°C.

[0250] Preferably, at least 75% by weight of monomers M1, based on the total amount of monomers M1 present in the monomers M, are present in the polymer phase (1).

[0251] The actual glass transition temperature depends on the monomer composition forming the respective polymer phases (1) and (2), and the theoretical glass transition temperature can be calculated from the monomer composition used in the emulsion polymerization. The theoretical glass transition temperature is generally calculated from the monomer composition by the Fox equation:

[0252] 1 / Tg t =x a / Tg a +x b / Tg b +....x n / Tg n ,

[0253] In this equation, x a , x b ....x n is the mass fraction of monomers a, b, ....n, and Tg a , Tg b , ....Tg n is the actual glass transition temperature of a homopolymer synthesized from only one of the monomers 1, 2, ....n at one time, in Kelvin. The Fox equation is described by TGFox in Bull. Am. Phys. Soc. Jan. 1956, p. 123, and in Ullmann's der technischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], Vol. 19, p. 18, 4th edition, Verlag Chemie, Weinheim, 1980. The actual Tg values ​​of homopolymers of most monomers are known and listed, for example in Ullmann's dertechnischen Chemie [Ullmann's Encyclopedia of Industrial Chemistry], 5th edition, volume A21, page 169, Verlag Chemie, Weinheim, 1992. Other sources for the glass transition temperature of homopolymers are, for example, J. Brandrup, EH Immergut, Polymer Handbook, 1st edition, J. Wiley, New York 1966, 2nd edition, J. Wiley, New York 1975, 3rd edition, J. Wiley, New York 1989, 4th edition, J. Wiley, New York 2004.

[0254] Generally, the theoretical glass transition temperature Tg according to the Fox calculation described herein is t The glass transition temperatures of the polymer phases (1) and (2) are similar or even identical to the experimentally determined glass transition temperatures described herein and deviate from each other by no more than 5 K, in particular by no more than 2 K. Accordingly, the actual and theoretical glass transition temperatures of the polymer phases (1) and (2) can be adjusted by selecting suitable monomers Ma, Mb ... Mn and their mass fractions x in the monomer composition. a 、x b …x n To achieve the desired glass transition temperatures Tg(1) and Tg(2) respectively. It is common knowledge for those skilled in the art to select suitable amounts of monomers Ma, Mb...Mg to obtain a copolymer and / or copolymer phase having a desired glass transition temperature.

[0255] The monomer composition forming the polymer phase (1) is preferably selected so that the theoretical glass transition temperature Tg t (1) is preferably in the range of 25 to +40° C., in particular in the range of -20 to 20° C. Likewise, the monomer composition forming the polymer phase (2) is selected so that the theoretical glass transition temperature Tg t (2) Preferably in the range of +50 to +150°C, more preferably in the range of 60 to 120°C.

[0256] In particular, the relative amounts of the monomers forming the polymer phase (1) and the monomers forming the polymer phase (2) are selected so that the monomers M comprise

[0257] 50 to 95% by weight, preferably 60 to 90% by weight, based on the total amount of monomers M, of monomers which form a polymer phase (1) having a lower glass transition temperature Tg(1),

[0258] 5 to 50% by weight, preferably 10 to 40% by weight, based on the total amount of monomers M, of monomers which form a polymer phase (2) having a higher glass transition temperature Tg(2).

[0259] Therefore, the polymer particles contained in the polymer dispersion obtained by the process of the present invention comprise:

[0260] 50 to 95% by weight, preferably 60 to 90% by weight, of a polymer phase (1) having a lower glass transition temperature Tg(1), based on the total weight of the polymer particles,

[0261] 5 to 50% by weight, preferably 10 to 40% by weight, of a polymer phase (2) having a higher glass transition temperature Tg(2), based on the total weight of the polymer particles.

[0262] It is obvious to a person skilled in the art that the monomers M forming the polymer phase (1) and the monomers M forming the polymer phase (2) may differ in terms of the type of monomers and / or their relative amounts. Obviously, the monomers M forming the polymer phase (2) will contain a greater amount of monomers that result in a higher glass transition temperature. In one group of embodiments, the relative amount of monomer M3 is greater in the monomers M forming the polymer phase (2) than in the monomers M forming the polymer phase (1). In another group of embodiments, the relative amount of monomer M3 is greater in the monomers M forming the polymer phase (1) than in the monomers M forming the polymer phase (2). However, the overall composition of the monomers M forming the polymer phase (1) and the monomers M forming the polymer phase (2) is within the range given above.

[0263] Preferably, the aqueous polymer dispersion of the invention has a pH of at least pH 6, for example in the range of pH 6 to pH 9.

[0264] The aqueous polymer dispersion of the present invention generally has a solid content in the range of 30 to 75% by weight, preferably 40 to 65% by weight, in particular 45 to 60% by weight. The solid content describes the proportion of the non-volatile part. The solid content of the dispersion is determined by an infrared moisture analysis balance. In this determination, a certain amount of polymer dispersion is introduced into the instrument, heated to 140°C and then kept at this temperature. Once the average weight reduction drops below 1 mg within 140 seconds, the measurement procedure is ended. The ratio of the weight after drying to the original mass introduced gives the solid content of the polymer dispersion. The total solid content of the preparation is determined by arithmetic calculation based on the amount of added substances and their solid content and concentration.

[0265] If the polymer in the polymer latex has functional groups that are complementary to the functional groups of the crosslinking agent, the polymer dispersion may contain a crosslinking agent for achieving post-crosslinking of the polymer latex particles. In this context, the term "complementarily" is understood to mean that the functional groups of the latex and the functional groups of the crosslinking agent are susceptible to chemical reactions that form chemical bonds between the atoms of the respective functional groups. Typically, the crosslinking agent has at least two functional groups that are complementary to the functional groups of the polymer of the polymer latex. Examples of suitable crosslinking agents are described below.

[0266] In addition to polymers and optional cross-linking agents, the aqueous polymer dispersion of the present invention can also contain other ingredients that are conventionally present in the aqueous polymer dispersion. These other ingredients are, for example, surface-active compounds such as emulsifiers and protective colloids, particularly those used to produce polymer latex, other defoamers and the like. Other ingredients can also be acid, alkali, buffer, decomposition products of polymerization, deodorizing compounds and chain transfer agents. In addition, polymer latex can contain biological azide compounds to avoid microbial corruption. The amount of each individual component is typically no more than 1.5 weight % based on the gross weight of the polymer dispersion. The total amount of these described components is typically no more than 5 weight % based on the gross weight of the polymer latex.

[0267] Preferably, the amount of volatile organic matter, ie the content of organic compounds with a boiling point up to 250° C. under standard conditions (101325 kPa) determined by gas chromatography according to ISO 17895:2005, is less than 0.5 wt %, in particular less than 0.2 wt %, based on the total weight of the polymer latex.

[0268] In addition to the polymer, the aqueous polymer latex also contains an aqueous phase in which the polymer particles of the polymer latex are dispersed. The aqueous phase, also referred to as the serum, consists essentially of water and any water-soluble other ingredients. The total concentration of any other ingredients is typically no more than 10% by weight, particularly no more than 8% by weight, based on the total weight of the aqueous phase.

[0269] The aqueous polymer latex of the present invention can be prepared by any method for preparing an aqueous dispersion of a polymer made from polymerized monomers M. In particular, the aqueous polymer latex of the present invention is prepared by aqueous emulsion polymerization, in particular by free radical aqueous emulsion polymerization of the monomers M. The term "free radical aqueous emulsion polymerization" means that the polymerization of the monomers M is initiated by free radicals formed by the decay of the polymerization initiator, whereby free radicals are formed in the polymerization mixture. Therefore, it is also called "free radical initiated emulsion polymerization". The process of free-radical initiated emulsion polymerization of monomers in aqueous medium has been widely described and is therefore sufficiently familiar to the person skilled in the art [see in this regard Emulsion Polymerization in Encyclopedia of Polymer Science and Engineering, Vol. 8, p. 659 ff. (1987); DC Blackley, in High Polymer Latices, Vol. 1, p. 35 ff. (1966); H. Warson, The Applications of Synthetic Resin Emulsions, Chapter 5, p. 246 ff. (1972); D. Diederich, Chemie in unserer Zeit 24, pp. 135 to 142 (1990); Emulsion Polymerisation, Interscience Publishers, New York (1965); DE-A 40 03422; and Dispersionen synthetischer Hochpolymerer, F. Springer-Verlag, Berlin (1969)]. Typical procedures for the aqueous emulsion polymerization of ethylenically unsaturated monomers are also described in the patent literature discussed in the introduction to this patent application.

[0270] The free-radical initiated aqueous emulsion polymerization is usually carried out by emulsifying the ethylenically unsaturated monomers in an aqueous medium forming the aqueous phase, usually by using surface-active compounds such as emulsifiers and / or protective colloids, and polymerizing the system using at least one initiator which decays by the formation of free radicals, thereby initiating the chain-growth addition polymerization of the ethylenically unsaturated monomers M. The preparation of the aqueous polymer dispersions according to the invention can differ from this general process only by the specific use of the above-mentioned monomers M1 to M8. It is here recognized that for the purposes of the present invention, the process shall also include the seeded, staged, single-shot and gradient mechanisms well known to those skilled in the art.

[0271] The free radical initiated aqueous emulsion polymerization is triggered by a free radical polymerization initiator (free radical initiator). In principle, these can be peroxides or azo compounds. Of course, redox initiator systems are also useful. In principle, the peroxide used can be an inorganic peroxide such as hydrogen peroxide, or a peroxodisulfate salt such as a mono- or di-alkali metal peroxodisulfate, or an ammonium salt of peroxodisulfate such as the mono- and disodium, potassium or ammonium salt, or an organic peroxide such as an alkyl hydroperoxide, such as tert-butyl hydroperoxide, The azo compounds used are essentially 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile) and 2,2'-azobis(amidopropyl)dihydrochloride (AIBA, corresponding to V-50 from Wako Chemicals). Oxidants suitable for redox initiator systems are essentially the peroxides detailed above. Corresponding reducing agents that can be used are sulfur compounds with a low oxidation state, for example alkali metal sulfites, such as potassium sulfite and / or sodium sulfite, alkali metal bisulfites, such as potassium sulfite and / or sodium bisulfite, alkali metal metabisulfites, such as potassium metabisulfite and / or sodium metabisulfite, formaldehyde sulfoxylates, such as potassium formaldehyde sulfoxylate and / or sodium formaldehyde sulfoxylate, alkali metal salts, in particular potassium or sodium salts of aliphatic sulfinic acids, and alkali metal hydrogen sulfides, such as potassium and / or sodium hydrogen sulfide, polyvalent metal salts, such as ferrous sulfate, ammonium ferrous sulfate, ferrous phosphate, enediols, such as dihydroxymaleic acid, dibenzoyl ketone and / or ascorbic acid, and reducing sugars, such as sorbitol, glucose, fructose and / or dihydroxyacetone.

[0272] Preferred free radical initiators are inorganic peroxides, especially peroxodisulfates.

[0273] Typically, the amount of free radical initiator used, based on the total amount of monomers M, is from 0.05 to 2 pphm, preferably from 0.1 to 1 pphm, based on the total amount of monomers M.

[0274] The amount of free radical initiator required for the emulsion polymerization of the monomers M can initially be completely loaded into the polymerization vessel. However, it is also possible to add no free radical initiator or only a portion of the free radical initiator, for example not more than 30% by weight, in particular not more than 20% by weight, based on the total amount of free radical initiator, and then add any remaining free radical initiator to the free radical polymerization reaction under polymerization conditions. Preferably, at least 70%, in particular at least 80%, in particular at least 90% or the total amount of polymerization initiator is input into the free radical polymerization reaction under polymerization conditions. The addition of the monomers M can be carried out according to the consumption in the free radical emulsion polymerization of the monomers M, in batches of one or more portions or at a constant or variable flow rate.

[0275] Generally, the term "polymerization conditions" is understood to mean the temperature and pressure during which the free-radical initiated aqueous emulsion polymerization proceeds at a sufficient polymerization rate. It depends in particular on the free-radical initiator used. Advantageously, the type and amount of free-radical initiator, the polymerization temperature and the polymerization pressure are selected so that there is always a sufficient amount of initiating free radicals to initiate or maintain the polymerization reaction.

[0276] Preferably, the free radical emulsion polymerization of the monomer M is carried out by a so-called feed process (also referred to as a monomer feed process), which means that at least 80%, in particular at least 90% or the entire amount of the monomer M to be polymerized is counted into the polymerization reaction under polymerization conditions during the metering period P. The addition can be carried out in batches, preferably continuously at a constant or variable feed rate. The duration of the period P can depend on the production equipment and can vary from, for example, 20 minutes to 12 hours. Often, the duration of the period P will be in the range of 0.5 hours to 8 hours, in particular in the range of 1 hour to 6 hours. In a multi-stage emulsion polymerization step, the total duration of all steps is typically within the above range. The duration of a single step is typically shorter. Preferably, similar to the addition of the monomers, at least 70%, in particular at least 80%, especially at least 90% or the total amount of the polymerization initiator is introduced into the emulsion polymerization.

[0277] Aqueous free radical emulsion polymerization is generally carried out in the presence of one or more suitable surfactants. These surfactants typically contain emulsifiers and provide micelles in which polymerization occurs and are used to stabilize monomer droplets and grow polymer particles during the aqueous emulsion polymerization process. The surfactant used in the emulsion polymerization is generally not separated from the polymer dispersion, but is retained in the aqueous polymer dispersion obtained by the emulsion polymerization of the monomers M.

[0278] The surfactant may be selected from emulsifiers and protective colloids. In contrast to emulsifiers, protective colloids are understood to refer to polymer compounds with a molecular weight higher than 2000 Daltons, while emulsifiers typically have lower molecular weights. The surfactant may be anionic or nonionic or a mixture of nonionic and anionic surfactants.

[0279] Anionic surfactants generally carry at least one anionic group, which is typically selected from phosphate, phosphonate, sulfate and sulfonate groups. Anionic surfactants carrying at least one anionic group are typically used in the form of their alkali metal salts, in particular in the form of their sodium salts or in the form of their ammonium salts.

[0280] Preferred anionic surfactants are anionic emulsifiers, in particular anionic emulsifiers with at least one sulfate or sulfonate group. Likewise, anionic emulsifiers with at least one phosphate or phosphonate group can be used, either as the sole anionic emulsifier or in combination with one or more anionic emulsifiers with at least one sulfate or sulfonate group.

[0281] Examples of anionic emulsifiers carrying at least one sulfate or sulfonate group are, for example,

[0282] -Alkyl sulfates, especially C8-C 22 - salts of alkyl sulfates, in particular alkali metal and ammonium salts,

[0283] - Sulfate monoesters of ethoxylated alkanols, especially ethoxylated C8-C 22 - sulfuric acid monoesters of alkanols, preferably salts having an ethoxylation level (EO level) in the range from 2 to 40, especially alkali metal salts and ammonium salts,

[0284] -Alkyl sulfonic acids, especially C8-C 22 - salts of alkylsulfonic acids, in particular alkali metal and ammonium salts,

[0285] - dialkyl esters of sulfosuccinic acid, especially di-C4-C 18 - salts of alkyl esters, in particular alkali metal and ammonium salts,

[0286] -Alkylbenzenesulfonic acid, especially C4-C 22 - salts of alkylbenzenesulfonic acids, in particular alkali metal and ammonium salts, and

[0287] - mono- or di-sulfonated alkyl-substituted diphenyl ethers, e.g., having C4-C 24 -alkyl bis(benzenesulfonic acid) ether salts, in particular alkali metal salts and ammonium salts. The latter are common knowledge, for example from US Pat. No. 4,269,749, and are commercially available, for example 2A1(Dow Chemical Company),

[0288] - surfactants having polymerizable ethylenically unsaturated double bonds as described herein, such as compounds of formula (I)-(IV), wherein X and Y are respectively SO3 - or O-SO3 - .

[0289] Examples of anionic emulsifiers with phosphate or phosphonate groups include, but are not limited to, the following salts selected from the following groups:

[0290] - Mono- and di-alkyl phosphates, especially C8-C 22- salts of alkyl phosphates, in particular alkali metal and ammonium salts,

[0291] - Phosphoric acid monoesters of C2-C3-alkoxyalkanols, preferably with an alkoxylation level in the range of 2 to 40, especially in the range of 3 to 30, e.g. ethoxylated C8-C 22 Phosphoric acid monoesters of -alkanols, preferably with an ethoxylation level (EO level) in the range of 2 to 40, propoxylated C8-C 22 Phosphoric acid monoesters of -alkanols, preferably having a propoxylation level (PO level) in the range of 2 to 40, and ethoxylated propoxylated C8-C 22 - Phosphoric acid monoesters of alkanols, preferably salts with an ethoxylation level (EO level) in the range of 1 to 20 and a propoxylation level in the range of 1 to 20, especially alkali metal salts and ammonium salts

[0292] -Alkylphosphonic acid, especially C8-C 22 - salts of alkylphosphonic acids, in particular alkali metal and ammonium salts, and

[0293] - Salts of alkylbenzenephosphonic acids, especially C4-C 22 - Salts of alkylbenzenephosphonic acids, in particular alkali metal and ammonium salts.

[0294] - Surfactants having polymerizable ethylenically unsaturated double bonds as described herein, such as compounds of formula (I)-(IV), wherein X and Y are respectively HPO3 - PO3 2 、O-HPO3 - or O-PO3 2 .

[0295] The anionic emulsifiers may also comprise emulsifiers having polymerizable double bonds, for example emulsifiers of formula (I) to (IV) and their salts, in particular alkali metal or ammonium salts:

[0296]

[0297] In formula (I), R 1 H, C1-C 20 -alkyl, C5-C 10 -cycloalkyl, optionally substituted by C1-C 20 - alkyl-substituted phenyl, R 2 and R 2 'All H or O, R 3 and R 4 is H or methyl, m is 0 or 1, n is an integer from 1 to 100, and X is SO3 - 、O-SO3 - 、O-HPO3- or O-PO3 2- .

[0298]

[0299] In formula (II), R is H, C1-C 20 -alkyl, C5-C 10 -cycloalkyl, optionally substituted by C1-C 20 - alkyl substituted phenyl, k is 0 or 1, X is SO3 - 、O-SO3 - 、O-HPO3 - or O-PO3 2- .

[0300]

[0301] In formula (III), R 1 H, C1-C 20 -alkyl, O-C1-C 20 -alkyl, C5-C 10 -cycloalkyl, O-C5-C 10 -cycloalkyl, optionally substituted by C1-C 20 -alkyl-substituted O-phenyl, n is an integer from 1 to 100, and Y is SO3 - 、HPO3 - or PO3 2- .

[0302]

[0303] In formula (IV), R 1 H, C1-C 20 -alkyl or 1-phenylethyl, R 2 H, C2-C 20 -alkyl or 1-phenylethyl, A is C2-C4-alkanediyl, such as 1,2-ethanediyl, 1,2-propylenediyl, 1,2-butanediyl or 1,4-butanediyl, n is an integer from 1 to 100, and Y is SO3 - 、HPO3 - or PO3 2- .

[0304] A specific embodiment of the copolymerizable emulsifier of formula (I) refers to a sulfate or phosphate of polyethylene glycol monoacrylate. A specific embodiment of the copolymerizable emulsifier of formula (I) can also refer to a phosphonate or allyl ether sulfate of polyethylene glycol monoacrylate. The commercially available copolymerizable emulsifier of formula (I) is Emulsifier, PAM emulsifier, PD and ADEKA PP-70.

[0305] The specific embodiment of the copolymerizable emulsifier of formula (II) also refers to alkyl allyl sulfonated succinate. The commercially available copolymerizable emulsifier of formula (II) is LF40.

[0306] The specific embodiment of the copolymerizable emulsifier of formula (III) also refers to branched unsaturated. The commercially available copolymerizable emulsifier of formula (III) is Reasoap emulsifier and KH.

[0307] The specific embodiment of the copolymerizable emulsifier of formula (IV) also refers to polyoxyethylene alkylphenyl ether sulfate and polyoxyethylene mono- or distyrylphenyl ether sulfate. The commercially available copolymerizable emulsifier of formula (IV) is BC and AR emulsifier.

[0308] Further suitable anionic surfactants can be found in Houben Weyl, Methoden der organischen Chemie [Methods of Organic Chemistry], Volume XIV / 1, Makromolekulare Stoffe [Macromolecular Substances], Georg Thieme Verlag, Stuttgart, 1961, pages 192-208.

[0309] Preferably, the surfactant comprises at least one anionic emulsifier with at least one sulfate or sulfonate group. At least one anionic emulsifier with at least one sulfate or sulfonate group can be the only type of anionic emulsifier. However, a mixture of at least one anionic emulsifier with at least one sulfate or sulfonate group and at least one anionic emulsifier with at least one phosphate or phosphonate can also be used. In this mixture, the amount of at least one anionic emulsifier with at least one sulfate or sulfonate group is preferably at least 50% by weight based on the total weight of the anionic surfactant used in the method of the present invention. In particular, the amount of the anionic emulsifier with at least one phosphate or phosphonate group is no more than 20% by weight based on the total weight of the anionic surfactant used in the method of the present invention.

[0310] Preferred anionic surfactants are anionic emulsifiers selected from the group consisting of:

[0311] -Alkyl sulfates, especially C8-C 22- salts of alkyl sulfates, in particular alkali metal and ammonium salts,

[0312] - Sulfate monoesters of ethoxylated alkanols, especially ethoxylated C8-C 22 - salts of sulfuric acid monoesters of alkanols, preferably with an ethoxylation level (EO level) in the range of 2 to 40, especially alkali metal salts,

[0313] - Sulfate monoesters of ethoxylated alkylphenols, especially ethoxylated C4-C 18 - salts, especially alkali metal salts, of sulfuric acid monoesters of alkylphenols (preferably with an ethoxylation level of 3 to 40),

[0314] -Alkylbenzenesulfonic acid, especially C4-C 22 - salts of alkylbenzenesulfonic acids, especially alkali metal salts,

[0315] - mono- or di-sulfonated alkyl-substituted diphenyl ethers, e.g., having C4-C 24 -Alkyl bis(benzenesulfonic acid) ether salts, especially alkali metal salts.

[0316] - a polymerizable emulsifier of formula (III).

[0317] Particularly preferred are anionic emulsifiers selected from the following groups, including mixtures thereof:

[0318] -Alkyl sulfates, especially C8-C 22 - salts of alkyl sulfates, in particular alkali metal and ammonium salts,

[0319] - Sulfate monoesters of ethoxylated alkanols, especially ethoxylated C8-C 22 - salts of sulfuric acid monoesters of alkanols, preferably with an ethoxylation level (EO level) in the range of 2 to 40, especially alkali metal salts,

[0320] - mono- or di-sulfonated alkyl-substituted diphenyl ethers, e.g., having C4-C 24 -Alkyl bis(benzenesulfonic acid) ether salts, especially alkali metal salts

[0321] - a polymerizable emulsifier of formula (III) wherein Y is SO3 - .

[0322] In addition to the anionic surfactants mentioned above, the surfactant may also comprise one or more nonionic surface-active substances, in particular selected from nonionic emulsifiers. Suitable nonionic emulsifiers are, for example, aromatic aliphatic or aliphatic nonionic emulsifiers, such as ethoxylated mono-, di- and trialkylphenols (ethoxylation level: 3 to 50, alkyl radical: C4-C 10), long chain alcohol ethoxylates (ethoxylation level: 3 to 100, alkyl radical: C8-C 36 ), and polyethylene oxide / polypropylene oxide homopolymers and copolymers. These may contain alkylene oxide units copolymerized in random distribution or in block form. Very suitable examples are EO / PO block copolymers. Preferred examples tend to be ethoxylates of long-chain alkanols, especially those with an average ethoxylation level of 5 to 100 alkyl free radicals C8C 30 Among these, a specific preferred example is a linear C 12 -C 20 Those having an alkyl radical and an average ethoxylation level of 10 to 50, and ethoxylated monoalkylphenols.

[0323] The surfactant used in the method of the invention generally comprises a total amount of not more than 30 wt % based on the surfactant used in the method of the invention, especially not more than 20 wt % of a nonionic surfactant, especially does not comprise any nonionic surfactant. A combination of at least one anionic surfactant and at least a nonionic surfactant may also be used. In this case, the weight ratio of the total amount of anionic surfactant to the total amount of nonionic surfactant is in the range of 99:1 to 70:30, particularly in the range of 98:2 to 75:25, particularly in the range of 95:5 to 80:20.

[0324] Preferably, the amount of surfactant is in the range of 0.2 to 5% by weight, in particular in the range of 0.3 to 4.5% by weight, based on the monomers M to be polymerized. In a multistage emulsion step emulsion polymerization, the amount of surfactant is generally in the range of 0.2 to 5% by weight, in particular in the range of 0.3-4.5% by weight, based on the total amount of monomers polymerized in each step.

[0325] Preferably, the major part, i.e. at least 80% of the surfactant used, is added to the emulsion polymerization in parallel with the addition of the monomers. In particular, the monomers are added as an aqueous emulsion to the polymerization with at least 80% of the surfactant used in the emulsion polymerization.

[0326] It has been found to be advantageous to carry out the free radical emulsion polymerization of the monomers M in the presence of a seed latex. The seed latex is a polymer latex present in the aqueous polymerization medium before the start of the polymerization of the monomers M. The seed latex can help to better adjust the particle size or the final polymer latex obtained in the free radical emulsion polymerization of the present invention.

[0327] In principle, every polymer latex can be used as seed latex. For the purpose of the present invention, seed latex is preferred in which the particle size of the polymer particles is relatively small. In particular, the Z average particle size of the polymer particles of the seed latex measured by dynamic light scattering (DLS) at 20° C. (see below) is preferably in the range of 10 to 80 nm, in particular 10 to 50 nm. Preferably, the polymer particles of the seed latex are made of ethylenically unsaturated monomers containing at least 95% by weight of one or more monomers, based on the total weight of the monomers forming the seed latex, selected from C2-C 10 -alkyl esters, in particular ethyl acrylate, n-butyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, C1-C4-alkyl methacrylates such as methyl methacrylate, monoethylenically unsaturated nitriles such as acrylonitrile and vinyl aromatic monomers such as styrene as defined above and mixtures thereof. In particular, the polymer particles of the seed latex are made from ethylenically unsaturated monomers comprising at least 95% by weight, based on the total weight of the monomers forming the seed latex, of one or more monomers selected from C1-C4-alkyl methacrylates such as methyl methacrylate, monoethylenically unsaturated nitriles such as acrylonitrile and vinyl aromatic monomers such as styrene as defined above and mixtures thereof.

[0328] For this reason, the seed latex is generally loaded into a polymerization vessel before the polymerization of the monomer M begins. In particular, the seed latex is loaded into the polymerization vessel and polymerization conditions are subsequently established, for example by heating the mixture to the polymerization temperature. Before the addition of the monomer M begins, it can be beneficial to load at least a portion of the free radical initiator into the polymerization vessel. However, it is also possible to add the monomer M and the free radical polymerization initiator in parallel into the polymerization vessel.

[0329] The amount of the seed latex may be generally in the range of 0.01 to 10 wt %, preferably 0.05 to 5 wt %, particularly 0.05 to 3 wt %, calculated as solid, based on the total weight of monomers in the monomer composition M to be polymerized.

[0330] The free radical aqueous emulsion polymerization of the present invention can be carried out at a temperature in the range of 0 to 170° C. The temperature employed is generally in the range of 50 to 120° C., commonly in the range of 60 to 120° C., typically in the range of 70 to 110° C. The free radical aqueous emulsion polymerization of the present invention can be carried out at a pressure less than, equal to or greater than 1 atm (atmospheric pressure), so the polymerization temperature can exceed 100° C. and can be up to 170° C. The polymerization of the monomers is usually carried out at ambient pressure, but can also be carried out at elevated pressure. In this case, the pressure can take values ​​of 1.2, 1.5, 2, 5, 10, 15 bar (absolute pressure) or even higher. If the emulsion polymerization is carried out under reduced pressure, a pressure of 950 mbar, commonly 900 mbar and typically 850 mbar (absolute pressure) is established. Advantageously, the free radical aqueous emulsion polymerization of the present invention is carried out at ambient pressure (about 1 atm) excluding oxygen, for example, under an inert gas atmosphere, for example under nitrogen or argon.

[0331] The method for producing the polymer latex of the present invention can be a single-stage polymerization or a multi-stage emulsion polymerization. In a single-stage polymerization, the overall composition of the monomers M fed to the polymerization reaction under the polymerization conditions remains the same or almost the same, while in a multi-stage emulsion polymerization, the overall composition of the monomers M fed to the polymerization reaction under the polymerization conditions is changed at least once, in particular so that the theoretical glass transition temperature of the resulting polymer formed in one stage differs from the theoretical glass transition temperature of the resulting polymer formed in another stage by at least 10°C, in particular at least 20°C or at least 40°C.

[0332] In a specific group of embodiments, the method of the present invention is carried out as a 2-stage emulsion polymerization, i.e., the composition of the monomers fed to the polymerization reaction is modified once under the polymerization conditions, or as a 3- or 4-stage emulsion polymerization, i.e., the composition of the monomers fed to the polymerization reaction is modified twice or three times under the polymerization conditions.

[0333] In particular, the aqueous emulsion polymerization is a multi-stage aqueous emulsion polymerization, which includes

[0334] i. Aqueous emulsion polymerization monomer composition M i The first stage corresponds to the theoretical glass transition temperature Tg in the range of -25°C to +40°C, in particular in the range of -20 to +20°C according to Fox. t (i) to obtain a first-stage polymer latex, and

[0335] ii. Aqueous emulsion polymerization monomer composition M ii The second stage, in the first stage polymer latex, wherein the monomer composition M iiThe glass transition temperature Tg in the range of 50 to 150° C., in particular in the range of 60 to 120° C., is in accordance with Fox. t (ii);

[0336] Or it may optionally include

[0337] i. Aqueous emulsion polymerization monomer composition M i The first stage corresponds to the theoretical glass transition temperature Tg in the range of 50°C to 150°C, in particular in the range of 60 to 120°C according to Fox. t (i) to obtain a first-stage polymer latex, and

[0338] ii. Aqueous emulsion polymerization monomer composition M ii The second stage, in the first stage polymer latex, wherein the monomer composition M ii Comply with the theoretical glass transition temperature Tg according to Fox in the range of -25 to +40°C, in particular in the range of -20 to +20°C t (ii);

[0339] In these multi-stage aqueous emulsion polymerizations, the monomer composition conforming to the theoretical glass transition temperature in the range of -25 to +40°C, in particular in the range of -20 to +20°C, preferably accounts for 50 to 95% by weight, more preferably 60 to 90% by weight, of the total amount of monomers M, while the monomer composition conforming to the theoretical glass transition temperature in the range of 50 to 150°C, in particular in the range of 60 to 120°C, preferably accounts for 5 to 50% by weight, more preferably 10 to 40% by weight, of the total amount of monomers M.

[0340] In a specific embodiment group, the aqueous emulsion polymerization is a multi-stage aqueous emulsion polymerization, which comprises

[0341] i. Aqueous emulsion polymerization monomer composition M i The first stage corresponds to the theoretical glass transition temperature Tg in the range of 50°C to 150°C, in particular in the range of 60 to 120°C according to Fox. t (i) to obtain a first-stage polymer latex, wherein the monomer composition M i Comprising a monomer composition M i 0.5 to 10% by weight of at least one monomer M4, based on the overall weight of

[0342] ii. Aqueous emulsion polymerization monomer composition M ii The second stage, in the first stage polymer latex, wherein the monomer composition M iiComply with the theoretical glass transition temperature Tg according to Fox in the range of -25 to +40°C, in particular in the range of -20 to +20°C t (ii) wherein the monomer composition M ii Comprising a monomer composition M ii at most 0.5% by weight of the overall weight of one or more monomers M4,

[0343] Wherein the polymer latex obtained in step i is neutralized to a pH of at least pH 5 before being subjected to the second stage of aqueous emulsion polymerization in step ii.

[0344] In this specific embodiment group, the monomer composition M i Preferably, it accounts for 5 to 50% by weight of the total amount of monomer M, more preferably 10 to 40% by weight, and the monomer composition M ii It preferably accounts for 50 to 95% by weight of the total amount of monomers M, preferably 60 to 90% by weight.

[0345] In this specific embodiment group, the monomer composition M i The polymerization is preferably carried out in the presence of a chain transfer agent as described below. The amount of the chain transfer agent may be in the range of 1:1 to 1:1 based on the monomer composition M. i The total amount is in the range of 0.05 to 8 wt %, particularly in the range of 0.1 to 4 wt %.

[0346] The polymerization of the monomers M can optionally be carried out in the presence of chain transfer agents. Chain transfer agents are understood to mean compounds which transfer free radicals, which reduce the molecular weight of the growing chain and / or control the chain growth in the polymerization. Examples of chain transfer agents are aliphatic and / or araliphatic halogen compounds, for example n-butyl chloride, n-butyl bromide, n-butyl iodide, dichloromethane, dichloroethane, chloroform, bromoform, trichlorobromomethane, dibromodichloromethane, carbon tetrachloride, carbon tetrabromide, benzyl chloride, benzyl bromide, organic sulfur compounds such as primary, secondary or tertiary aliphatic mercaptans, for example ethanethiol, n-propyl mercaptan, 2-propyl mercaptan, n-butyl mercaptan, 2-butyl mercaptan, 2-methyl-2-propyl mercaptan, n-pentyl mercaptan, 2-pentyl mercaptan, 3-pentyl mercaptan, 2-methyl-2-butyl mercaptan, 3-methyl-2-butyl mercaptan, n-hexyl mercaptan, 2-hexyl mercaptan, 3-hexyl mercaptan, 2-methyl-2-pentyl mercaptan, 3-methyl-2-pentyl mercaptan, thiols, 4-methyl-2-pentanethiol, 2-methyl-3-pentanethiol, 3-methyl-3-pentanethiol, 2-ethylbutanethiol, 2-ethyl-2-butanethiol, n-heptanethiol and its isomeric compounds, n-octanethiol and its isomeric compounds, n-nonanethiol and its isomeric compounds, n-decanethiol and its isomeric compounds, n-undecanethiol and its isomeric compounds, n-dodecanethiol and its isomeric compounds, n-tridecathiol and its isomeric compounds, substituted thiols, for example 2-hydroxyethanethiol, aromatic thiols such as benzenethiol, o-, m- or p-methylbenzenethiol, thioglycolic acid (thioglycolic acid The invention relates to alkyl esters of thioglycolic acid), such as 2-ethylhexyl thioglycolate, alkyl esters of mercaptopropionic acid, such as octyl mercaptopropionate, and other sulfur compounds described in Polymer Handbook, 3rd edition, 1989, J. Brandrup and EH Immergut, John Wiley and Sons, Section II, pages 133 to 141, but also aliphatic and / or aromatic aldehydes, such as acetaldehyde, propionaldehyde and / or benzaldehyde, unsaturated fatty acids, such as oleic acid, dienes with non-conjugated double bonds, such as divinylmethane or vinylcyclohexane, or hydrocarbons with readily abstractable hydrogen atoms, for example toluene.

[0347] Alternatively, it is possible to use mixtures of the aforementioned chain transfer agents which do not interfere with each other. The total amount of chain transfer agents optionally used in the process according to the invention, based on the total amount of monomers M, generally does not exceed 2% by weight, in particular 1% by weight, based on the total amount of monomers M. However, during a particular stage of the polymerization, the amount of chain transfer agent added to the polymerization may be a value exceeding 2% by weight, based on the total amount of monomers M added to the polymerization in said stage, and may be up to 8% by weight, in particular up to 4% by weight.

[0348] It is often advantageous when the aqueous polymer dispersion obtained after the polymerization of the monomers M is subjected to an aftertreatment in order to reduce the residual monomer content. This aftertreatment can be achieved chemically, for example by using more effective free-radical initiator systems (referred to as afterpolymerization) to complete the polymerization reaction, and / or physically, for example by stripping the aqueous polymer dispersion with steam or an inert gas. The corresponding chemical and physical methods are familiar to the person skilled in the art—see, for example, EP-A 771 328, DE-A 196 24 299, DE-A 196 21 027, DE-A 19741184, DE-A 19741187, DE-A 19805122, DE-A 198 28183, DE-A 1989 39199, DE-A 19840586 and DE-A 19847115. The combination of chemical and physical aftertreatment has the advantage of removing not only unconverted ethylenically unsaturated monomers but also other disruptive volatile organic components (VOCs) from the aqueous polymer dispersion.

[0349] Since the polymer contained in the aqueous polymer dispersion may contain acidic groups from monomer M4 and optionally from a polymerization initiator, the aqueous polymer dispersion obtained by the method of the present invention is often neutralized before being formulated into a coating composition. The neutralization of the acid groups of the polymer is achieved by a neutralizing agent known to those skilled in the art after polymerization and / or during polymerization. For example, the neutralizing agent can be added in a co-feed with the monomers to be polymerized or in a separate feed. Suitable neutralizing agents include organic amines, alkali metal hydroxides, ammonium hydroxide. In particular, neutralization is achieved by using ammonia or alkali metal hydroxides such as sodium hydroxide or potassium hydroxide.

[0350] In addition, it may be appropriate to formulate the polymer latex of the present invention with a post-curing agent. Ideally, such a post-curing agent, also known as a post-crosslinking agent, will produce a crosslinking reaction during and / or after film formation by forming coordination or covalent bonds with reactive sites on the surface of the polymer particles.

[0351] Crosslinking agents suitable for providing post-crosslinking are, for example, compounds having at least two functional groups selected from oxazoline, amino, aldehyde, aminooxy, carbodiimide, aziridine, epoxy and hydrazide groups, derivatives or compounds with acetoacetyl groups. These crosslinking agents react with reactive sites of polymers of the polymer dispersion with complementary functional groups in the polymer, which are able to form covalent bonds with the crosslinking agent. Suitable systems are known to those skilled in the art.

[0352] Since the polymers contained in the polymer dispersions of the present invention carry carboxyl groups, post-crosslinking can be achieved by formulating the polymer dispersion with one or more polycarbodiimides, such as those described in US 4977219, US 5047588, US 5117059, EP 0277361, EP 0507407, EP 0628582, US 5352400, US 2011 / 0151128 and US 2011 / 0217471. It is assumed that the crosslinking effect is based on the reaction of the carboxyl groups of the polymer with the polycarbodiimide. This reaction typically results in covalent crosslinks based primarily on N-acylurea bonds (JW Taylor and DR Bassett, in EJ Glass (ed.), Technology for Waterborne Coatings, ACS Symposium Series 663, Am. Chem. Soc., Washington, DC, 1997, Chapter 8, pp. 137-163).

[0353] Likewise, since the polymer particles contained in the polymer dispersion of the present invention carry carboxyl groups derived from monomer M4, suitable post-curing agents may also be water-soluble or water-dispersible polymers carrying oxazoline groups, such as the polymers described in US5300602 and WO 2015 / 197662.

[0354] Post-crosslinking can also be achieved by methods similar to EP 1227116, which describes aqueous two-component coating compositions containing a binder polymer with carboxylic acid and hydroxyl functional groups and a polyfunctional crosslinker having functional groups selected from isocyanate, carbodiimide, aziridine and epoxy groups.

[0355] If the polymer in the polymer dispersion carries keto groups, for example by using monomers M5c, such as diacetone acrylamide (DAAM), then post-crosslinking can be achieved by formulating the aqueous polymer dispersion with one or more dihydrazides, in particular aliphatic dicarboxylic acids such as adipic acid dihydrazide (ADDH) as described in US 4931494, US 2006 / 247367 and US 2004 / 143058. These components react substantially during and after film formation, although a certain degree of preliminary reaction can occur.

[0356] Other suitable agents for achieving post-curing include

[0357] - epoxy silanes that crosslink carboxyl groups in the polymer;

[0358] - dialdehydes such as glyoxal or acetoacetoxy groups for crosslinking urea groups, such as those derived from monomers M5b and M5c, respectively, as defined herein, in particular urea (meth)acrylate or acetoacetoxyethyl (meth)acrylate;

[0359] - di- and / or polyamines crosslinking keto or epoxy groups, such as those derived from monomers M5c or M6b as defined herein;

[0360] - UV initiators such as benzophenones, including benzophenone, 4-methoxybenzophenone, 4-methylbenzophenone, 2,4,6-trimethylbenzophenone, acetophenones such as 2-hydroxy-2,2-dimethylacetophenone, 2-phenyl-2,2-dimethylacetophenone, cycloalkylphenyl ketones such as 1-benzoylcyclohexane-1-ol (=1-hydroxycyclohexylphenyl ketone) and benzophenone and mixtures thereof, in particular liquid mixtures such as mixtures of 4-methylbenzophenone and benzophenone, mixtures of 2,4,6-trimethylbenzophenone and benzophenone and mixtures of 1-hydroxycyclohexylphenyl ketone and benzophenone.

[0361] Suitable systems are, for example, the UV initiators described in EP 355028, EP 441221, EP 0789724, US Pat. No. 5,516,453 and US Pat. No. 5,498,659 and / or commercially available, for example from Omnirad and IGM Resins (eg Esacore TZM, Esacure TZT, Omnirad 4MBZ).

[0362] The present invention also relates to an aqueous coating composition containing the polymer latex of the present invention as a binder or as a co-binder. In particular, the present invention also relates to an aqueous coating composition wherein the polymer latex is the only binder or accounts for at least 80% of the binder contained in the coating composition.

[0363] The aqueous coating composition of the present invention can be formulated as a clear coating or as a lacquer. In the latter case, in addition to the polymer latex, the aqueous coating composition also contains at least one inorganic pigment which imparts a white shade or color to the coating obtained when the aqueous coating is used to coat a substrate.

[0364] According to the definition in the German standard specification DIN 55944:2003-11, pigments for the purposes of the present invention are practically insoluble, finely dispersed organic or preferably inorganic colorants. Examples of pigments are in particular inorganic pigments, for example white pigments such as titanium dioxide (CI Pigment White 6), and also colored pigments, for example:

[0365] - black pigments, for example iron oxide black (CI Pigment Black 11), iron manganese black, spinel black (CI Pigment Black 27), carbon black (CI Pigment Black 7);

[0366] - Colored pigments, such as chromium oxide, hydrated chromium oxide green; chromium green (CI Pigment Green 48); cobalt green (CI Pigment Green 50); ultramarine green; cobalt blue (CI Pigment Blue 28 and 36); ultramarine blue, iron blue (CI Pigment Blue 27), manganese blue, ultramarine violet, cobalt violet, manganese violet, iron oxide red (CI Pigment Red 101); cadmium sulphoselenide (CI Pigment Red 108); molybdate red (CI Pigment Red 104); ultramarine red,

[0367] - Iron oxide brown, mixed brown, spinel and corundum phases (CI Pigment Brown 24, 29 and 31), chrome orange;

[0368] - Iron oxide yellow (CI Pigment Yellow 42); nickel titanium yellow (CI Pigment Yellow 53; CI Pigment Yellow 157 and 164); chrome titanium yellow; cadmium sulfide and cadmium zinc sulfide (CI Pigment Yellow 37 and 35); chrome yellow (CI Pigment Yellow 34), zinc yellow, alkaline earth metal chromates; Naples yellow; bismuth vanadate (CI Pigment Yellow 184);

[0369] Interference pigments, such as metallic effect pigments based on coated metal flakes, pearlescent pigments based on mica flakes coated with metal oxides, and liquid-crystalline pigments.

[0370] The aqueous coating composition may also contain one or more fillers. Examples of suitable fillers are aluminosilicates such as feldspar, silicates such as kaolin, talc, mica, magnesite, alkaline earth metal carbonates such as calcium carbonate, for example calcium carbonate in the form of calcite or chalk, magnesium carbonate, dolomite, alkaline earth metal sulfates such as calcium sulfate, silicon dioxide, etc. In the coating composition of the present invention, finely divided fillers are naturally preferred. Fillers can be used in the form of individual components. However, in practice, filler mixtures have been found to be particularly useful, such as calcium carbonate / kaolin, calcium carbonate / talc. Glossy paints generally contain only a small amount of very finely divided fillers or do not contain any fillers. Fillers also include matting agents that significantly reduce gloss as needed. Matting agents are generally transparent and can be organic or inorganic. Examples of matting agents are inorganic silicates, such as those from WR Grace & Company. Brand and from Evonik GmbH Brand. Organic matting agents can be obtained from and BYK-Chemie GmbH and Deuteron under the brand acquired by Deuteron GmbH under the brand name.

[0371] The proportion of pigments and fillers in an aqueous coating composition can be described in a manner known per se by the pigment volume concentration (PVC). The PVC describes the ratio of the volume of pigment (VP) and the volume of filler (VF) relative to the total volume, consisting of the volume of binder (VB), the volume of pigment (VP) and the volume of filler in the dry coating film, expressed as a percentage: PVC [%] = (VP + VF) x 100 / (VP + VF + VB)

[0372] If the aqueous coating composition is formulated as a paint, it generally has a pigment volume concentration (PVC) of at least 5%, in particular at least 10%, and typically will not exceed 90%, in particular 85%. In a specific group of embodiments, the PVC will not exceed a value of 60%, in particular 50%, and in particular in the range of 5 to 60% or 5 to 50%. However, the inventive effect of the polymer dispersion is also manifested in varnishes, which typically have a pigment / filler content of less than 5% by weight based on the varnish and correspondingly have a PVC of less than 5%. In another group of embodiments, the PVC will be in the range of >60 to 90%, in particular in the range of 65 to 85%.

[0373] According to one embodiment group, the aqueous coating composition of the present invention is designed as a paint containing white pigment - that is, it comprises at least one white pigment and optionally one or more fillers. As white pigment, it particularly comprises titanium dioxide, preferably in the form of rutile, optionally in combination with one or more fillers. Particularly preferably, the coating composition of the present invention comprises white pigment, more particularly titanium dioxide, preferably in the form of rutile, in combination with one or more fillers (e.g. chalk, talcum or a mixture thereof).

[0374] In another preferred embodiment group, the aqueous coating composition of the present invention is designed as a clearcoat or wood stain formulation. Compared with lacquers, clearcoats are substantially devoid of pigments and fillers, while wood stains do not contain much fillers, i.e., have a PVC of less than 5%.

[0375] According to a specific embodiment group, the present invention also relates to an aqueous coating composition (hereinafter also referred to as an aqueous coating composition), comprising:

[0376] i) at least one aqueous polymer latex as defined above;

[0377] ii) Titanium dioxide pigment.

[0378] According to another specific embodiment group, the present invention also relates to the use of the aqueous polymer latex as a binder in an aqueous coating composition containing titanium dioxide pigment.

[0379] In the above-mentioned embodiment, aqueous polymer latex and TiO Pigment slurry or paste combination.For the preparation of aqueous TiO of aqueous coating composition The TiO of pigment slurry or paste Concentration is generally based on aqueous TiO in each case The gross weight of pigment slurry or paste 30 to 85 weight%, often 40 to 80 weight%.For the preparation of the titanium dioxide pigment of the aqueous dispersion of pigment slurry or paste can be any TiO conventionally used in coating composition, particularly aqueous coating composition Pigment.Usually, use this TiO Pigment, wherein TiO Particle is preferably rutile form.In another preferred embodiment, TiO Particle also can be for example coated with aluminum, silicon and zirconium compound.

[0380] Typically, the weight ratio of the polymer to the titanium dioxide pigment is in the range of ≥0.1:5.0 to ≤5.0:0.1; preferably, the weight ratio of the polymer to the titanium dioxide pigment is in the range of ≥0.5:5.0 to ≤5.0:0.5; in particular, more preferably, the weight ratio of the polymer to the titanium dioxide pigment is in the range of ≥0.5:3.0 to ≤3.0:0.5, in particular, in the range of ≥0.5:1.5 to ≤1.5:0.5.

[0381] Preferably, the titanium dioxide pigment has an average primary particle size in the range of ≧0.1 μm to ≦0.5 μm, as determined by light scattering or electron microscopy.

[0382] Typically, the aqueous coating composition further comprises at least one additive selected from thickeners, defoamers, leveling agents, film-forming aids, biocides, wetting agents or dispersants, fillers and coalescing agents.

[0383] The aqueous coating composition can be prepared simply by mixing TiO2 pigment powder or an aqueous slurry or paste of TiO2 pigment with the aqueous polymer latex of the present invention, preferably by applying shear to the mixture, for example by using a dissolver commonly used to prepare waterborne paints. It is also possible to prepare an aqueous slurry or paste of TiO2 pigment and the aqueous polymer latex of the present invention and then incorporate or mix it with other polymer latexes of the present invention or any other polymer latex binder.

[0384] Aqueous dispersions of polymer composites can also be prepared by incorporating the aqueous polymer latex of the present invention as a binder or co-binder into a water-based formulation of a paint that already contains TiO2 pigment, for example by mixing the aqueous polymer latex of the present invention with a pigment formulation that already contains other additives conventionally used in paint formulations.

[0385] In order to stabilize the TiO2 pigment particles in the aqueous pigment slurry or paste, it can be optionally mixed in the presence of additives (e.g., dispersants) conventionally used in aqueous pigment slurries or pigment pastes. Suitable dispersants include, but are not limited to, for example, polyphosphates such as sodium polyphosphate, potassium polyphosphate or ammonium polyphosphate, alkali metal salts and alkali metal and ammonium salts of acrylic acid homopolymers or copolymers or maleic anhydride polymers, polyphosphonates such as 1-hydroxyethane-1,1-disodium phosphate and naphthalenesulfonates, especially their sodium salts.

[0386] The polymer concentration in the aqueous polymer latex for preparing the aqueous dispersion of the polymer composite is generally 10 to 70% by weight, preferably 20 to 65% by weight and most preferably 30 to 60% by weight, based on the total weight of the aqueous polymer latex in each case.

[0387] In addition to the polymer latex of the present invention, titanium dioxide pigment and optionally conventional binders, the aqueous coating composition may contain one or more pigments other than the above-mentioned TiO2 pigment and / or filler.

[0388] Preferably, the aqueous coating composition comprises at least one aqueous polymer latex as defined herein, further comprising a rheology modifier. Suitable rheology modifiers include associative thickener polymers and non-associative rheology modifiers. The aqueous liquid composition preferably comprises a thickener selected from an associative thickener and optionally a non-associative thickener.

[0389] Associative thickener polymers are well known and frequently described in the scientific literature, for example EJ Schaller et al., "Associative Thickeners" in Handbook of Coating Additives, Vol. 2 (ed. LJ Calbo), Marcel Decker 192, pp. 105-164, J. Bieleman "PUR-Verdicker" in Additives for Coatings (ed. J. Bielemann), Wiley 2000, pp. 50-58. NiSAT thickener polymers of the HEUR and HMPE types are also described in the patent literature, such as US 4,079,028, US 4155,892, EP 61822, EP 307775, WO 96 / 31550, EP 612329, EP 1013264, EP 1541643, EP 1584331, EP 2184304, DE 4137247, DE 102004008015, DE 102004031786, US 2011 / 0166291 and WO 2012 / 052508. In addition, associative thickener polymers are commercially available.

[0390] Associative thickener polymers include anionic, acrylate thickener polymers, so-called HASE polymers (hydrophobically modified polyacrylate thickeners), which are copolymers of acrylic acid and alkyl acrylate monomers, wherein the alkyl group of the alkyl acrylate may have from 6 to 24 carbon atoms. Associative thickener polymers also include nonionic associative thickeners, so-called NiSAT thickeners (nonionic synthetic associative thickeners), which are generally linear or branched block copolymers having at least one internal hydrophilic portion, particularly a polyether portion, especially at least one polyethylene oxide portion and two or more terminal hydrocarbon groups, each terminal hydrocarbon group having at least 4 carbon atoms, particularly 4 to 24 carbon atoms, such as linear or branched alkyl radicals having from 4 to 24 carbon atoms or alkyl-substituted phenyl groups having from 7 to 24 atoms. NiSAT thickeners include hydrophobically modified polyethylene oxide polyurethane rheology modifiers, also known as HEUR or PUR thickeners, and hydrophobically modified polyethylene oxide, also known as HMPE.

[0391] The amount of associative thickener polymer depends on the desired viscosity profile and is usually in the range of 0.05 to 2.5 wt %, particularly 0.1 to 2 wt % thickener, especially 0.2 to 2 wt %, based on the latex paint.

[0392] Suitable non-associative rheology modifiers are in particular thickeners based on cellulose, in particular hydroxyethylcellulose, but also thickeners based on acrylate emulsions (ASE). Among the non-associative rheology modifiers, preference is given to non-associative cellulose-based thickeners.

[0393] The amount of thickener polymer depends on the desired viscosity profile and is often in the range of 0.05 to 2.5 wt %, in particular 0.1 to 2 wt % thickener, in particular 0.15 to 1.5 wt %, based on the latex paint.

[0394] The aqueous coating composition of the present invention also comprises conventional additives. Conventional additives will depend on the type of coating in a well-known manner, including but not limited to:

[0395] - wetting agents or dispersants,

[0396] - Film-forming aids, also known as coalescing agents,

[0397] - Leveling agent,

[0398] -UV stabilizers,

[0399] -Biocide

[0400] - Defoamers / deaerators.

[0401] Suitable wetting agents or dispersants are, for example, sodium, potassium or ammonium polyphosphates, alkali metal and ammonium salts of acrylic acid copolymers or maleic anhydride copolymers, polyphosphonates, such as sodium 1-hydroxyethane-1,1-diphosphonate, and naphthalenesulfonates, especially the sodium salts thereof.

[0402] Suitable film-forming aids are solvents and plasticizers. Compared with the solvent, the plasticizer has a low volatility, preferably a boiling point above 250° C. at 1013 mbar, while the solvent has a higher volatility than the plasticizer, preferably a boiling point below 250° C. at 1013 mbar. Suitable film-forming aids are, for example, white spirit, pine oil, propylene glycol, ethylene glycol, butanediol, butyl glycol acetate, butyl glycol diacetate, butyl diglycol, butyl carbitol, 1-methoxy-2-propanol, 2,2,2-trimethyl-1,3-pentanediol monoisobutyrate and glycol ethers and esters, available, for example, from BASF SE as and and Purchased from Dow The amount is preferably <5% by weight, more preferably <1% by weight, based on the overall formulation. The formulation may also be completely free of film-forming aids. If the coating composition contains film-forming aids, these are preferably selected from plasticizers. Typically, the coating composition does not require any film-forming aids.

[0403] Further suitable auxiliaries and components are described, for example, by J. Bieleman in “Additives for Coatings”, Whiley VCH, Weinheim 2000; by TCPatton in “Paint Flow and Pigment Dispersions”, 2nd edition, John Whiley & Sons 1978; by M. Schwartz and R. Baumstark in “Water based Acrylates for Decorative Coatings”, Curt R. Vincentz Verlag, Hanover 2001.

[0404] The aqueous coating composition of the present invention can also be formulated as a low VOC paint. In this case, the concentration of volatile compounds in the coating composition is preferably less than 0.1% by weight, more preferably less than 0.05% by weight, based on the total amount of the aqueous coating composition. According to the present invention, volatile compounds are compounds having a boiling point of less than 250° C. at 1013 mbar.

[0405] The aqueous coating composition of the present invention is particularly suitable for coating wooden substrates such as wood or wooden materials. The aqueous coating composition of the present invention is particularly suitable for architectural coatings, i.e. for coating the outdoor or indoor parts of buildings. In this case, the substrate can be a mineral substrate, for example plaster of Paris, gypsum, gypsum board or concrete, wood, wooden materials, metal, wallpaper or plastics, for example PVC.

[0406] The aqueous coating composition can be applied to the substrate to be coated in a typical manner, for example by application with a brush or roller, by spraying, by dipping, by rolling or by rod coating onto the desired substrate. Preferred application is by brush and / or roller.

[0407] Generally, the coating of the substrate is achieved in such a way that the substrate is first coated with the aqueous coating composition of the invention and the aqueous coating thus obtained is then subjected to a drying step, especially in a temperature range of ≥-10°C and ≤+50°C, advantageously ≥+5 and ≤+40°C, particularly advantageously ≥+10 and ≤+35°C.

[0408] The substrate coated with the water-based coating composition of the present invention has excellent resistance to whitening when in contact with water or weathering environment. In addition, when containing two or more polymer phases, the coating has high anti-blocking properties. And the coating obtained by using the coating composition of the present invention is not easy to form the cracks often observed when the water-based coating composition is applied to the wooden substrate. In addition, they are stable and anti-aging, and will not produce undesirable viscosity increase during storage.

[0409] The invention will now be illustrated by the following non-limiting examples.

[0410] 1. Abbreviations:

[0411] ADDH: adipic acid dihydrazide

[0412] AM: Acrylamide

[0413] AMA: Allyl Methacrylate

[0414] AS: Acrylic

[0415] DAAM: diacetone acrylamide

[0416] DLS D[v,4.3] values ​​determined by dynamic light scattering

[0417] EHA:2-Ethylhexyl acrylate

[0418] area% Area percentage

[0419] FuselA: Fusel alcohol-acrylate

[0420] i-BuA: Isobutyl acrylate

[0421] MAS:Methacrylic acid

[0422] MMA:Methyl Methacrylate

[0423] MeHQ 4-Methoxyphenol (Hydroquinone Monomethyl Ether)

[0424] MEMO: 3-Methacryloxypropyl-trimethoxysilane

[0425] n-BuA: n-Butyl acrylate

[0426] pphm: parts per 100 monomers

[0427] PVC pigment / volume concentration

[0428] PTZ Phenothiazine

[0429] RH:Relative humidity

[0430] RT: Room temperature (22-23℃)

[0431] rpm: revolutions per minute

[0432] S:Styrene

[0433] SC: Solid content

[0434] UMA: 25% solution of imidazolin-2-yl-ethyl methacrylate in methyl methacrylate

[0435] wt%: weight%

[0436] Here and hereinafter the terms "room temperature" and "ambient temperature" refer to a temperature in the range of 22-23°C.

[0437] 2. Analysis of polymer latex

[0438] 2.1 Solid content

[0439] The solids content is determined by drying a defined amount of aqueous polymer dispersion (about 2 g) in an aluminum crucible with an inner diameter of about 5 cm in a drying cabinet at 130° C. to constant weight (2 hours). Two separate measurements are performed. The values ​​reported in the examples are the average of two measurements.

[0440] 2.2 Particle size

[0441] If not stated otherwise, the average particle size of the polymer latex was determined by dynamic light scattering (DLS) as described above using a Malvern HPPS.

[0442] The weighted average particle size of the polymer latex can also be determined by HDC. The measurement is performed using a PL-PSDA particle size distribution analyzer (Polymer Laboratories, Inc.). A small amount of the polymer latex sample is injected into an aqueous eluent containing an emulsifier to obtain a concentration of about 0.5 g / l. The mixture is pumped through a glass capillary of about 15 mm in diameter filled with polystyrene balls. Due to their hydrodynamic diameter, smaller particles can spatially enter slower flowing areas in the capillary, so that on average smaller particles experience a slower elution flow. Finally, a UV detector that measures extinction at a fixed wavelength of 254 nm is used to monitor the component separation.

[0443] 2.3 Brookfield viscosity

[0444] Viscosity was measured according to standard method DIN EN ISO 3219:1994 at 20°C using a "Brookfield RV" model laboratory viscometer with a #4 or #5 spindle at 100 revolutions per minute.

[0445] 2.4 Glass transition temperature Tg

[0446] The glass transition temperature is determined by the DSC method (Differential Scanning Calorimetry, 20 K / min, midpoint measurement, DIN 53765:1994-03) and a DSC instrument (Q 2000 series from TA Instruments).

[0447] 3. Emulsifier, monomer, seed latex

[0448] Emulsifier 1: 45 wt% C12-alkyl diphenyl ether disulfonate sodium ( 2A1) aqueous solution

[0449] Emulsifier 2: Ethoxylated C with 18EO 16 / C 18 A 20 wt% aqueous solution of alkanol ( AT18)

[0450] Emulsifier 3: 27 wt % aqueous solution of sodium lauryl ether sulfate ( FES 27)

[0451] Emulsifier 4: 15 wt% aqueous solution of sodium dodecyl sulfate ( SDS 15)

[0452] Emulsifier 5: 25 wt% aqueous solution of sulfated ethoxylated alkyl glycerol allyl ether sodium salt of formula (III), degree of ethoxylation = 10 (Adeka Reasoap SR-1025)

[0453] Emulsifier 6: Ethoxylated isocyanate with 8EO 13 20 wt% aqueous solution of alkanol (Lutensol TO82)

[0454] Seed latex 1: Polyacrylate latex with a solid content of 33.00 wt% and a D[v,4.3] value of 30 nm

[0455] Seed latex 2: polystyrene latex with a solid content of 33.00 wt% and a D[v,4.3] value of 30 nm

[0456] Sodium hydroxymethanesulfinate ( C)

[0457] Ureaethyl methacrylate (UMA): 25 wt% solution of imidazolin-2-one-1-yl-ethyl methacrylate in methyl methacrylate

[0458] PAM 100: Hydroxyethyl methacrylate phosphate half ester

[0459] Isobutyl acrylate: Isobutyl acrylate with a biochar content of 57%, obtained from BCH Brühl-Chemikalien Handel GmbH

[0460] Isoamyl acrylate See scheme below

[0461] Bio-isoamyl acrylate A mixture of 2-methylbutyl acrylate and 3-methylbutyl acrylate in a weight ratio of 1:4 - see the following scheme

[0462] Fusel Oil Acrylate: Fusel Oil Acrylate: synthesized by esterification of acrylic acid with fusel oleyl alcohol (purified by distillation), with 63% biochar; contains about 87% (iso)amyl acrylate (mixture of 2-methyl and 3-methylbutyl isomers) + 10% isobutyl acrylate - production see scheme below

[0463] Scheme for producing acrylic fusel oil:

[0464] 464 g of fusel alcohol obtained as a side stream of bioethanol production (containing 10.5% by weight of water and 89.5% by weight of an organic fraction containing 12.4% by area of ​​isobutanol and 80% by area of ​​a mixture of 2-methylbutanol and 3-methylbutanol), 400 mL of cyclohexane, 4.5 g of a stabilizer solution containing 3.33% by weight of MeHQ and 8.33% by weight of 50% by weight of hypophosphorous acid, 3.5 g of a 5% by weight copper(II) acetate solution were charged into a 2 L four-necked flask equipped with a crescent stirrer, a water separator with an intensive condenser, a gas feed tube and a thermometer. 377.5 g of glacial acrylic acid (stabilized with 200 ppm of MeHQ) and 28.5 g of p-toluenesulfonic acid monohydrate were added. The water separator was filled with cyclohexane.

[0465] The reaction mixture was then heated. At a bath temperature of 110° C., water was separated while introducing air. 160 g of water were distilled off. After a reaction time of 5.5 h, the mixture was cooled. 400 mL of water were added to the reaction mixture at an internal temperature of 50° C.

[0466] After separation of the aqueous phase, a mixture of 375 mL of water and 150 mL of 12.5 wt % NaOH water was added. After separation of the aqueous phase, the organic phase was rinsed with 500 mL of 15 wt % NaCl aqueous solution. 877 g of a crude solution was obtained, to which 0.9 g of phenothiazine was added, and the solution was concentrated to 65 mbar at 60° C. and 100 mbar by a rotary evaporator. The product was then distilled off at a bath temperature of 70° C. and a pressure of 20 mbar. 491.2 g of fusel oil acrylate was obtained, which was stabilized with 100 mg of MeHQ. The product was clear and colorless and was analyzed by gas chromatography. It contained 11.5 area % of isobutyl acrylate and 84.0 area % of a mixture of 2-methylbutyl acrylate and 3-methylbutyl acrylate in a ratio of 20:80, which was determined by 1 H NMR determination.

[0467] Scheme for producing isoamyl acrylate:

[0468] 1058 g of isoamyl alcohol (petrochemical origin), 823 g of cyclohexane, 11.4 g of a stabilizer solution consisting of 3.33% by weight of MeHQ and 8.33% by weight of 50% by weight hypophosphorous acid and 8.4 g of a 5% by weight copper(II) acetate solution are placed in a heatable 4 L double-walled glass reactor equipped with a thermosensor, anchor stirrer, water separator, intensive condenser and air supply. 951 g of glacial acrylic acid (stabilized with 200 ppm of MeHQ) are then added. 95.4 g of 65% p-toluenesulfonic acid are added and heated. Water is distilled at a bottom temperature of 82 to 101° C.

[0469] 278 mL of water with a water content of 95.5% were separated. After 5.5 h, the reaction was stopped. After cooling, the reaction mixture was first extracted with 700 mL of water, then with a mixture of 500 mL of water and 400 g of a 12.5% ​​NaOH solution, then with 800 mL of water, the aqueous phase being separated in each case. After the last phase separation, 1 g of MeHQ was added to the organic phase, which was then fractionated at a pressure of 230 to 50 mbar. The internal temperature was raised from 44 ° C to 81 ° C. 1532 g of isoamyl acrylate, still containing 0.18 area % of isoamyl alcohol, was obtained, with a GC purity of 99.1 area % and a color number of 5 Hazen, and was stabilized with 100 ppm of MeHQ.

[0470] Scheme for the production of bio-isoamyl acrylate:

[0471] Ethyl acrylate (2555 g), MeHQ (3.6 g), phenothiazine (1.5 g) and 1000 g of isoamyl alcohol obtained by fractional distillation of a side stream from the production of bioethanol (2-methylbutanol and 3-methylbutanol in a ratio of 1:4, determined by 1H NMR) were introduced and heated in a 4 L heatable double-walled glass reactor with a heated lid, with a supply of rarefied air and stirring, the reactor being equipped with a three-stage cross-blade stirrer, a 50 cm column (Montz A3-750 packing), a cooler, a phase separator, a thermosensor and a gas inlet tube. Tetraisopropoxytitanium (36.06 g) was added at an internal temperature of 70° C.

[0472] After the start of boiling, the start-up was started with a reflux ratio (R:D) of 5:1. During the first 4h, ethyl acrylate was fed to the bottom in batches in an amount corresponding to the distillate. Within 4h, 111g of PTZ solution in ethanol (0.01 wt%) was added to the top of the column. Bottom samples were collected at periodic intervals and analyzed by gas chromatography to monitor the reaction process. During the next 6 hours, the pressure was gradually reduced to 550mbar and the reflux ratio was gradually adjusted to 2:5 (R:D). When the conversion rate was >99%, the ethyl acrylate was first fractionated and then the desired product was fractionated. The pressure was further reduced to 80mbar. The fractions with a purity of >98% were combined. 1272g of bio-isoamyl acrylate (a 1:4 mixture of 2-methylbutyl acrylate and 3-methylbutyl acrylate) with a purity of 99.2% were obtained. The product was stabilized with 100ppm of MeHQ.

[0473] 4. Preparation Examples

[0474] 4.1 Comparative Examples C1 to C2 and Examples D1 to D4 of the Invention:

[0475] Emulsion A was prepared by mixing 345 g of water, 8.2 g of acrylic acid, 18.9 g of acrylamide, 8.7 g of emulsifier 1, 12.6 g of emulsifier 2 and the respective amounts of monomers given in Table 1.

[0476] Initiator solution I was prepared by dissolving 0.9 g of sodium persulfate in 12.7 g of deionized water.

[0477] An oxidizing solution O was prepared by dissolving 0.5 g of tert-butyl hydroperoxide in 5 g of deionized water.

[0478] Reducing solution R was prepared by dissolving 0.9 g of sodium sulfite in 7 g of deionized water mixed with 0.4 g of acetone.

[0479] A reaction vessel equipped with an agitator and three separate feed lines was charged with 182 g of deionized water and 17 g of emulsifier 4, and the vessel was preheated to 95° C. After reaching a temperature of 95° C., 3.3% of emulsion A was fed into the vessel together with 25% of initiator solution I, and the mixture was stirred at 95° C. for 10 minutes. Thereafter, while maintaining 95° C., the remaining emulsion A was fed into the reaction vessel over 120 minutes. Starting at the same time as emulsion A, the remaining initiator solution I was fed into the reaction vessel through a separate feed line over 120 minutes. After the addition of emulsion A and initiator solution I was completed, stirring was continued at 95° C. for an additional 15 minutes. The vessel was then cooled to 90° C., and 2.7 g of ammonia (25% by weight of the solution) diluted with 4.0 g of water was added to the vessel. Thereafter, oxidizing solution O and reducing solution R were fed into the reaction vessel in parallel over 60 minutes through separate feed lines. After the addition of the oxidizing and reducing solutions had been completed, the vessel was cooled to room temperature and 2.4 g of ammonia (25 solution weight %) diluted with 15 g of water was added.

[0480] 4.2 Comparative Example C3 and Examples of the Invention D5 and D6:

[0481] Emulsion A was prepared by mixing 265 g of water, 13 g of acrylic acid, 13 g of acrylamide, 16 g of emulsifier 3, 7 g of emulsifier 2 and the respective amounts of monomers given in Table 1.

[0482] Initiator Solution I was prepared by dissolving 7.65 g of sodium persulfate in 101.57 g of deionized water.

[0483] An oxidizing solution O was prepared by dissolving 2.52 g of tert-butyl hydroperoxide in 22.67 g of deionized water.

[0484] Reducing solution R was prepared by dissolving 1.44 g of sodium sulfite in 15.36 g of deionized water mixed with 0.85 g of acetone.

[0485] A reaction vessel equipped with an agitator and three separate feed lines was charged with 265 g of deionized water and 30 g of seed latex 1, and the mixture was preheated to 83° C. After reaching a temperature of 83° C., Emulsion A was fed into the reaction vessel over 120 minutes while maintaining 83° C. Starting at the same time as Emulsion A, the remaining initiator solution I was fed into the reaction vessel through a separate feed line over 120 minutes. After the addition of Emulsion A and the initiator solution was completed, the reaction mixture was stirred at 83° C. for an additional 20 minutes.

[0486] Thereafter, oxidizing solution O and reducing solution R were fed in parallel to the reaction vessel via separate feed lines over 60 minutes at 83° C. After the addition of oxidizing solution and reducing solution had been completed, the vessel was cooled to room temperature and 3 g of aqueous ammonia (25%) and 15 g of water were added.

[0487] Table 1

[0488]

[0489] 1) Theoretical relative amount of biochar in polymer latex, calculated from the reported amount of biochar in isobutanol (this value can be determined by mass spectrometry). 12 C / 14 C ratio was determined experimentally).

[0490] 2) Measured relative amount of biochar in polymer latex as determined according to ASTM D6866-18 (Method B); measurements performed at the Curt-Engelhorn Center for Archaeometry (Mannheim, Germany)

[0491] 4.3 Comparative Example C4

[0492] Under a nitrogen atmosphere, 586.0 g of deionized water, 13.2 g of emulsifier 5 and 20.8 g of a 3 wt % aqueous solution of tetrasodium pyrophosphate were charged to a polymerization vessel equipped with a metering device and temperature regulation at 20 to 25° C. (room temperature). The initial charge was heated to 80° C. with stirring. When this temperature was reached, a homogeneous solution of 3.0 g of sodium persulfate in 39.9 g of deionized water was added and stirred at 80° C. for 2 minutes. Thereafter, emulsion feed 1 was started and emulsion feed 1 was metered in over 45 minutes while maintaining a temperature of 80° C. After completion of emulsion feed 1, polymerization was continued at 80° C. for 10 minutes. Then 26.9 g of a 25 wt % aqueous ammonia solution (the amount required to completely neutralize the methacrylic acid from emulsion feed 1) and 3.7 g of deionized water were added and stirred for 10 minutes.

[0493] Emulsion feed 1 (homogeneous mixture):

[0494] 139.7g deionized water

[0495] 4.4g emulsifier 5

[0496] 34.0 g methacrylic acid

[0497] 27.2g ureidoethyl methacrylate

[0498] 210.8g methyl methacrylate

[0499] 34.0g n-butyl acrylate

[0500] 170.0 g of a 20 wt% aqueous solution of diacetone acrylamide

[0501] 15.7 g 2-ethylhexyl thioglycolate

[0502] Subsequently, emulsion feed 2 was started. When 50% of this feed had been metered in over 45 minutes, a homogeneous solution of 0.5 g of sodium persulfate in 6.6 g of deionized water was metered in parallel over a further 45 minutes; the total feed time for emulsion feed 2 was 90 minutes.

[0503] Emulsion feed 2 (homogeneous mixture):

[0504] 188.4g deionized water

[0505] 7.6g emulsifier 5

[0506] 198.0g n-butyl acrylate

[0507] 224.4 g of 2-ethylhexyl acrylate

[0508] 237.6g methyl methacrylate

[0509] After completion of emulsion feed 2, the polymerization mixture was further reacted by stirring at 80° C. for 30 minutes. 130.8 g of deionized water were then added and stirring was continued at 70° C. for another 90 minutes. The obtained aqueous polymer dispersion was then cooled to room temperature. 141.7 g of a 12% strength by weight aqueous solution of adipic dihydrazide was added at room temperature. Finally, the dispersion was filtered through a 125 μm filter.

[0510] The solids content of the resulting aqueous polymer dispersion was 42.9% by weight. Upon dilution with deionized water, the weighted average particle size of the aqueous polymer dispersion was 37 nm (measured by HDC).

[0511] 4.4 Embodiments D7 to D14 of the present invention

[0512] By a procedure analogous to the protocol of Example C4 replacing the monomers in Feeds 1 and 2 with the respective relative amounts of pphm summarized and given in Table 2, polymer latexes of Inventive Examples D7 to D14 were prepared.

[0513] Table 2

[0514]

[0515]

[0516] 1) Brookfield viscosity

[0517] 2) Bio-C: The theoretical relative amount of biochar in the polymer latex (this value can be determined by mass spectrometry 12 C / 14 C ratio was determined experimentally)

[0518] 4.5 Comparative Example C5

[0519] In a polymerization vessel equipped with a metering device and temperature controlled at 22°C,

[0520] 341.9 g deionized water and

[0521] 55.0g emulsifier 4

[0522] Add and heat to 87° C. in a nitrogen atmosphere while stirring. At 80° C., add 43.0 g of feed 2 and 3.2 g of a 7% by weight aqueous sodium peroxodisulfate solution and heat the mixture further to 87° C. After 5 minutes, start feeds 1 and 2 (remaining amount), which are metered into the reaction vessel over 120 minutes. After the end of feeds 1 and 2, postpolymerization is carried out for 5 minutes. Then, feeds 3 and 4 are metered into the reaction vessel over 45 minutes.

[0523] Feed 1:

[0524] 13.7 g of a 7 wt% aqueous solution of sodium persulfate

[0525] Feed 2 (emulsion containing):

[0526] 526.1g deionized water

[0527] 36.7g emulsifier 4

[0528] 8.0g acrylic acid

[0529] 9.0 g 50 wt% acrylamide aqueous solution

[0530] 313.0g methyl methacrylate

[0531] 448.7g 2-Ethylhexyl acrylate

[0532] 42.5 g of a 25% by weight solution of ureido methacrylate in methyl methacrylate Feed 3:

[0533] 5.1 g 7 wt% sodium persulfate aqueous solution

[0534] Feed 4 (emulsion containing):

[0535] 272.9g deionized water

[0536] 13.9g emulsifier 4

[0537] 8.0g acrylic acid

[0538] 42.5 g of a 25% by weight solution of ureido methacrylate in methyl methacrylate 232.9 g of methyl methacrylate

[0539] After feeds 3 and 4 were complete, the polymerization mixture was reacted at 87° C. for 30 minutes; 5.3 g of a 25% by weight aqueous ammonia solution and 55.4 g of deionized water were then added. The mixture was cooled to 82° C. and stirred for 60 minutes. At the same time, 22.9 g of a 7.7% by weight aqueous hydrogen peroxide solution and 22.8 g of a 6.8% by weight aqueous L-ascorbic acid solution were metered into the reaction vessel. After this, 15.4 g of a 7.1% by weight aqueous ammonia solution were added; the mixture was cooled to 22° C. and the aqueous polymer dispersion was filtered through a 125 μm filter.

[0540] The resulting polymer latex had a solid content of 44.2% according to HDC, a pH value of 7.7, and an average particle size of 68 nm.

[0541] 4.6 Embodiments D15 to D22 of the present invention

[0542] By an analogous procedure to the protocol of Example C5 replacing the monomers with the respective relative amounts of pphm summarized and given in Table 3, polymer latexes of Inventive Examples D15 to D22 were prepared.

[0543] Table 3

[0544]

[0545]

[0546] 1) BF: Brookfield viscosity at 20°C

[0547] 2) Bio-C: The theoretical relative amount of biochar in the polymer latex (this value can be determined by mass spectrometry 12 C / 14 C ratio was determined experimentally)

[0548] 3) %C-Bio [measured]: The measured relative amount of biogenic carbon in the polymer latex as determined according to ASTM D6866-18 (Method B).

[0549] 4.6 Comparative Example C6

[0550] Under nitrogen atmosphere, a polymerization reaction vessel equipped with metering device and temperature regulation was charged at room temperature with 145.9 g of deionized water and 0.8 g of 33 wt% polystyrene seed latex 2. The initial charge was heated to 85° C. with stirring. When this temperature was reached, 7.1 g of a 7 wt% solution of sodium persulfate in deionized water was added and stirred at 85° C. for 5 minutes.

[0551] Thereafter emulsion feed 1 was started and metered over 113 minutes while maintaining a temperature of 85° C. Simultaneously, 21.4 g of a 7 wt % solution of sodium persulfate in deionized water were added to the polymerization vessel over a period of 180 minutes.

[0552] Emulsion feed 1 (homogeneous mixture):

[0553] 155.0g deionized water

[0554] 13.4g emulsifier 3

[0555] 149.1g n-butyl acrylate

[0556] 59.0g 2-Ethylhexyl acrylate

[0557] 166.0g styrene

[0558] 1.0gMEMO

[0559] Emulsion feed 2 was started immediately after emulsion feed 1 and was metered in over the course of 37 minutes.

[0560] Emulsion feed 2 (homogeneous mixture):

[0561] 52.5g deionized water

[0562] 4.5g emulsifier 3

[0563] 5.0g PAM 100

[0564] 49.7g n-butyl acrylate

[0565] 19.6g 2-ethylhexyl acrylate

[0566] 50.6 g styrene

[0567] After completion of emulsion feed 2, 6.1 g of deionized water were added and the polymerization mixture was reacted further for 30 minutes at 85° C. with stirring. After partial neutralization with 0.8 g of 25% by weight aqueous ammonia, 16.3 g of deionized water were added and stirring was continued at 85° C. for a further 5 minutes. Subsequently, 15.0 g of a 10% by weight aqueous solution of tert-butyl hydroperoxide and 12.2 g of a 13% by weight aqueous solution of acetone hydrogensulfite were metered in parallel over 120 minutes. 90 minutes after the start of this chemical deodorization step, 14.5 g of a 10% by weight solution of sodium hydroxide in deionized water were added to the mixture over 30 minutes. The aqueous polymer dispersion obtained was then cooled to room temperature and 15.8 g of rinse water were added. Finally, the dispersion was filtered through a 125 μm filter.

[0568] The solids content of the resulting aqueous polymer dispersion was 51.7% by weight. Upon dilution with deionized water, the weighted average particle size of the aqueous polymer dispersion was 338 nm (measured by HDC).

[0569] 4.7 Embodiment D23 of the present invention

[0570] By a procedure analogous to the protocol of Example C6 replacing the monomers with the respective relative amounts of pphm summarized and given in Table 4, the polymer latex of Inventive Example D23 was prepared.

[0571] Table 4:

[0572]

[0573]

[0574] 1) Bio-C: The theoretical relative amount of biochar in the polymer latex (this value can be determined by mass spectrometry 12 C / 14 C ratio was determined experimentally)

[0575] 4.8 Embodiment D24 of the present invention

[0576] In a reactor equipped with a stirrer, temperature control, nitrogen inlet and multiple injection possibilities, 855 g of deionized water, 95.5 g of seed latex 2 were charged. The reaction mixture was purged with nitrogen and heated to 85° C. 17.3 g of feed 2 was added at 85° C. After 5 minutes, feed 1 and feed 2 were added within 180 minutes. Feed 1: 1345.2 g of deionized water, 64.7 g of emulsifier 1, 72.8 g of emulsifier 6, 24.3 g of acrylic acid, 48.5 g of 50 wt % aqueous acrylamide solution, 1425.9 g of isobutyl acrylate, 950.6 g of methyl methacrylate. Feed 2: 69.3 g of sodium persulfate aqueous solution (7 wt %). The reaction mixture was postpolymerized at 85° C. for 30 minutes. Feed 3 and feed 4 were added within 60 minutes. Feed 3: 24.3 g of tert-butyl hydroperoxide aqueous solution (10 wt %). Feed 4: 21.8 g of aqueous sulfite solution (10 wt %). The reaction mixture was then cooled to ambient temperature and neutralized with aqueous sodium hydroxide solution to pH 8-9.

[0577] Tg (dry dispersion): 21°C

[0578] Average particle size (DLS): 130nm

[0579] Solid content: 46.1% by weight

[0580] 4.9 Comparative Example C7

[0581] In a reactor equipped with a stirrer, temperature control, nitrogen inlet and multiple injection possibilities, 855 g of deionized water, 95.5 g of seed latex 2 were charged. The reaction mixture was purged with nitrogen and heated to 85° C. 17.3 g of feed 2 were added at 85° C. After 5 minutes, feed 1 and feed 2 were added within 180 minutes. Feed 1: 1345.2 g of deionized water, 64.7 g of emulsifier 1, 72.8 g of emulsifier 6, 24.3 g of acrylic acid, 48.5 g of acrylamide (50% by weight in water), 1261.0 g of butyl acrylate, 1115.5 g of methyl methacrylate. Feed 2: 69.3 g of an aqueous solution of sodium persulfate (7% by weight). The reaction mixture was postpolymerized at 85° C. for 30 minutes. Feed 3 and feed 4 were added within 60 minutes. Feed 3: 24.3 g of an aqueous solution of tert-butyl hydroperoxide (10% by weight). Feed 4: 21.8 g of aqueous sulfite solution (10 wt %). The reaction mixture was then cooled to ambient temperature and neutralized with aqueous sodium hydroxide solution to pH 8-9.

[0582] Tg (dry dispersion): 20℃

[0583] Average particle size (DLS): 127nm

[0584] Solid content: 47.9% by weight

[0585] 5. Application performance of polymer latex

[0586] 5.1 Water absorption

[0587] The polymer latex was diluted to 25 wt %. Then, the latex was cast onto a rubber sheet (6.7*14.9 cm) to obtain a transparent film with a thickness of about 750 μm after drying. The film was placed on a frame with gauze for 7 days to completely dry. Then 2 films (2*2 cm) were cut out and weighed. Then, the film pieces were stored separately in deionized water in a 100 ml glass bottle for 24 hours (w 干 Then, it was taken out of the deionized water, gently wiped to remove all adhering water droplets, and weighed again (w 湿 ). The water absorption is calculated by the following formula and expressed in weight %:

[0588]

[0589] The results are summarized in Table 6.

[0590] 5.2 Elongation at break

[0591] The elasticity of polymer latex films (Examples C1, C2, C3 and D1 to D6) or paint films was measured according to DIN 53504. Free films with a dry film thickness of about 500 μm were prepared and dried at room temperature for 28 days. Each specimen was then cut into five S2 bone shapes and the actual film thickness was measured. The film thickness was measured at 200 mm / min at room temperature. -1 The elongation measurement is carried out at a fixed tensile speed to obtain the elongation at break in % compared to the initial specimen length and the elongation in Nmm -2 Both values ​​are reported as the average of five measurements.

[0592] The results are summarized in Table 6.

[0593] 5.3 Preparation formula

[0594] The polymer latexes of Examples C5 and D15 to D22 were tested in the following varnish formulations. For this purpose, the respective polymer latexes were treated to a solids content of 45% by weight by adding water and formulated as a letdown by mixing the latex with deionized water, a film preservative Actcide MKN 9 from Thor GmbH) and a deaerator (Tego Airex 902W, Evonik). Table 5 gives the respective amounts.

[0595] The paste was prepared by weighing the individual components given in Table 5 in a polyethylene beaker and homogenized by a dynamic mixer (Speedmixer™ DAC 600.1 FVZ from Hauschild GmbH & Co) according to the following scheme: 1 minute at 800 rpm, 1 hour at 1000 rpm, 2 minutes at 1250 rpm, 2.3 minutes at 1600 rpm. The paste was then divided into different portions and added to the different letdowns prepared previously and then homogenized with a dynamic mixer according to the following scheme: 1 minute at 800 rpm, 1 minute at 1000 rpm, 1 minute at 1250 rpm, 1.3 minutes at 1600 rpm.

[0596] Table 5

[0597]

[0598] 5.4 Whitening / Blistering

[0599] Glass plates were treated / cleaned according to ISO 1522: 100 micron wet films of the coating formulations described in Section 5.3 or of the polymer latex (Examples C1, C2, C3 and D1 to D6 and D15 to D22) were cast on clean glass using a thin film applicator (Erichsen Rakel) and dried for 1 day at RT (23° C.) and RH (50%). A black background below the glass plate provided contrast. A large drop of deionized water (approximately 3 cm in diameter) was placed on the coating and a stopwatch was started. Photographic records and annotations were given after different exposure times (0 = anhydrous whitening, 5 = opaque white). The results are summarized in Tables 6 and 7.

[0600] In the same experiment, the foaming was evaluated and ranked on a scale of 0 to 2. 0 means no visible foam, 1 means a few small foams, and 2 means many large foams. The results are summarized in Table 7.

[0601] 5.5 Pendulum hardness test

[0602] according to The pendulum hardness was determined as described in ISO 1522. For this purpose, a 100 μm wet film of the coating formulation described in Section 5.3 was cast on clean glass using a thin film applicator (Erichsen Rakel) and dried for the specified time. The pendulum hardness was then measured. The results are summarized in the following Table 8.

[0603] 5.6 Anti-adhesion

[0604] The blocking resistance was evaluated as follows. Six pine specimens were oriented in parallel, side by side in direct contact. The wood specimens were cut in the same way (cuts along the tangential direction) and the growth rings were oriented in the same direction. In the middle area of ​​the panel, the coating formulation described in Section 5.3 was applied by an applicator with a 300 μm wet layer. For the blocking resistance test, only the four middle-coated specimens were used.

[0605] The coating was dried at 23°C / 50% relative humidity for 24 hours. Two panels were stacked crosswise with the coated areas facing each other. The same was done for the second set of panels. A 5 kg (200 g / cm 2 ) and the panels were stored in a climate chamber at 23°C (RH=50%). After 24 hours, the weights were removed and the boards were separated by hand.

[0606] Block resistance was assessed by the force and degree of damage to separate the panels by hand according to the following scale:

[0607] 0 = no adhesion (adhesion), force required to separate wi / o;

[0608] 1 = slight adhesion;

[0609] 2 = low adhesion;

[0610] 3 = medium adhesion;

[0611] 4 = strong adhesion;

[0612] 5 = Very strong adhesion, the panels cannot be separated by hand.

[0613] The results are summarized in Table 8.

[0614] 5.7 Durability against UV radiation

[0615] The durability of the coating against UV radiation was carried out according to EN9276. For this purpose, pine panels were coated with the coating formulation described in Section 5.3. Apart from this, the experimental procedure was identical to that of EN927-6. The panels were removed after a specified interval of ~500h and gloss measurements were carried out at an angle of 60° according to DIN 53778. The values ​​reported here represent gloss retention in % relative to the initial value. The results are summarized in Table 9.

[0616] Table 6

[0617]

[0618] 1) Evaluation after 40 minutes, using polymer latex itself

[0619] Table 7

[0620]

[0621] Table 8

[0622]

[0623]

[0624] Table 9

[0625]

[0626] 5.8 Preparation formula

[0627] The polymer latexes of Examples C6 and D23 were tested in the following high PVC formulation (PVC = 77%).

[0628] The pastes were prepared by weighing the individual components given in Table 10 in a polyethylene beaker and homogenizing at 1600 rpm for 5 minutes by means of a dynamic mixer (Speedmixer™ DAC 600.1 FVZ from Hauschild GmbH & Co). After aging for 24 hours, the pastes were homogenized a second time at 1600 rpm for 15 minutes. Subsequently, the respective polymer emulsions were added to the pastes together with a variable amount of deionized water to account for a total solids content of 62.8% by weight of the paint and homogenized at 200 rpm for 3 minutes.

[0629] Table 10:

[0630]

[0631]

[0632] 5.8 Wet scrub resistance / opacity

[0633] Opacity, respectively hiding power, reflects the ability of a coating to cover a substrate. It can be quantified by spreading rate measurements. These measurements are made by applying different film thicknesses using a draw-down bar, i.e. a doctor blade (e.g. 150, 200, 220 and 250 microns wet) onto a defined contrast paper, such as Leneta foil with black and white areas and subsequent contrast measurements. These values ​​are then interpolated to produce the so-called spreading rate, which is the number of film thicknesses per area [m2] required to cover the substrate with a given contrast. 2 / L] is the reciprocal of the volume of the paint (reciprocal of the film thickness), for example 99.5% for a class I hiding paint or 98% for a class II hiding paint according to ISO DIN 13300.

[0634] The wet scrub resistance (WSR) of the prepared latex paints was tested by the nonwoven pad method according to ISO 11998. The WSR is assessed based on the weight loss per unit area due to abrasion and calculated back to a given average thickness loss in μm.

[0635] Table 11:

[0636]

[0637] The data in Table 11 show that the emulsion of Example D23 has better wet scrub resistance and higher coating rate than the emulsion of Comparative Example C6, resulting in a waterborne coating composition with better opacity.

[0638] 5.9 Semi-gloss paint with polymer emulsions D24 and C7

[0639] The following ingredients are used in semi-gloss paint:

[0640]

[0641] a) Semi-gloss of D24 latex

[0642] 315 g of Kronos 4311 pigment was mixed with 15 g of water. 1.75 g of AMP-95 neutralizer (Angus Chemical Company), 5 g of propylene glycol (Univar), 2 g of Foamstar 2420 defoamer (BASF), 9 g of Tamol 165A dispersant (Dow) and 3 g of Hydropalat WE 3320 wetting agent (BASF) were added at a low stirring speed. 1.5 g of Attagel 50 (BASF), 25 g of Minex 10 (Sibelco) filler and 20 g of Aquaflow NHS-310 (Ashland) nonionic associative thickener were added at a high stirring speed and mixed for 30 minutes. Subsequently, 81 g of deionized water was added and the mixture was filtered through a 400 μm filter. Then 524.77 g of the adhesive from Example 1, 25 g of Ropaque Ultra E polymer pigment (Dow), 2 g of Foamstar 2420 defoamer (BASF), 9 g of Texanol coalescent (Eastman) and 7.7 g of Optifilm 400 coalescent (Eastman) were added and mixed for 5 minutes. Then 2 g of Proxel AQ biocide (Lonza), 3 g of Polyphase 663 fungicide (Troy Corporation) and 3.7 g of Rheolate CVS 10 nonionic associative thickener (Elementis) were added and mixed for 5 minutes. Finally, 1.7 g of Acrylsol RM 895 nonionic associative thickener (Dow) was added and the mixture was stirred at medium stirring speed for 30 min.

[0643] b) Semi-gloss C7 latex

[0644] 315 g of Kronos 4311 pigment was mixed with 15 g of water. 1.75 g of AMP-95 neutralizer (Angus Chemical Company), 5 g of propylene glycol (Univar), 2 g of Foamstar 2420 defoamer (BASF), 9 g of Tamol 165A dispersant (Dow) and 3 g of Hydropalat WE 3320 wetting agent (BASF) were added at a low stirring speed. 1.5 g of Attagel 50 (BASF), 25 g of Minex 10 (Sibelco) filler and 20 g of Aquaflow NHS-310 (Ashland) nonionic associative thickener were added at a high stirring speed and mixed for 30 minutes. Subsequently, 104 g of deionized water was added and the mixture was filtered through a 400 μm filter. Then 505.05 g of the adhesive from Example 2, 25 g of Ropaque Ultra E polymer pigment (Dow), 2 g of Foamstar 2420 defoamer (BASF), 9 g of Texanol coalescent (Eastman) and 7.5 g of Optifilm 400 coalescent (Eastman) were added and mixed for 5 minutes. Then 2 g of Proxel AQ biocide (Lonza), 3 g of Polyphase 663 fungicide (Troy Corporation) and 4.5 g of Rheolate CVS 10 nonionic associative thickener (Elementis) were added and mixed for 5 minutes. Finally, 2 g of Acrylsol RM 895 nonionic associative thickener (Dow) was added and the mixture was stirred at medium stirring speed for 30 min.

[0645] 5.10 Application properties of semi-gloss paints with polymer latexes of Example 24 and Comparative Example C7

[0646] The low shear viscosity was measured according to ASTM D562 at 20° C. 7 days after the semi-gloss paint was prepared. The results are summarized in Table 12.

[0647] High shear viscosity was measured according to ASTM D4287 at 20° C. 7 days after the semi-gloss paint was prepared. The results are summarized in Table 12.

[0648] Opacity: Films were prepared using a 3 mil thinning bar on a Leneta 3B black and white sealed thinning card. The film was dried at room temperature for 24 hours. Opacity was determined spectrophotometrically as the ratio of reflected light from the dry coating on the black and white portions of the Leneta card. Opacity represents the ability of the coating to cover a black surface. The results are summarized in Table 12.

[0649] Gloss: Films were prepared from semi-gloss paint using a 3 mil thinning bar on Leneta 3B black and white sealed thinning cards. The films were dried at room temperature for 24 hours. Gloss was measured at 20°, 65° and 80° angles using a gloss meter. The results are summarized in Table 12.

[0650] The scrub resistance of semi-gloss paints containing polymer latex D24 or C7 was determined according to ASTM D2486. The scrub cycles were measured before failure occurred. The results are summarized in Table 12.

[0651] The yellowness index was determined according to ASTM E313 in a rapid UV test according to ASTM D4587, cycle 4, 1000 h. The results are summarized in Table 12.

[0652] Table 12

[0653] Paint with latex D24 Paint with latex C7 Low shear viscosity, 7 days [KU] 93.3 92.6 High Shear Viscosity, 7 Days [Poise] 0.66 0.60 Opacity 97.8 97.5 Gloss 20° 14.0 11.3 Gloss 65° 50.4 47.5 Glossiness 80° 83.7 79.3 Scrub resistance (cycles before failure) 1069 985 Yellowness Index (ASTM E313) 0.85 0.82

[0654] Midcoat and aluminum adhesion were measured according to ASTM D3359. The results for the semi-gloss paint containing polymer latex D24 were comparable to the semi-gloss paint containing polymer latex C7.

[0655] Stain removal according to ASTM D4828: Results for semi-gloss paint containing polymer latex D24 were comparable to those for polymer latex C7 for pencil, lipstick, crayon, ballpoint pen, red wine, ketchup, coffee, mustard (visual inspection)

[0656] Dirt Absorption: The ground glaze on the yellow pine surface was scrubbed with water and dried overnight. The substrate was divided into multiple sections according to the number of samples to be tested. Using an appropriate brush, the test paint samples were applied at a natural application rate. The coatings were cured at room temperature for 4 hours and 24 hours respectively. Then, half of the coating area was covered with 2 inches of dry dirt (Arizona or Carpet soil). The panel was allowed to stand for 15 minutes, then it was tilted vertically and tapped to release the dirt. The dirty area of ​​each sample was lightly brushed (15 times).

[0657] The dirt left on the panels coated with the semi-gloss paint containing polymer latex D24 was slightly less than the dirt left on the panels coated with the semi-gloss paint containing polymer latex C7 (visual assessment).

Claims

1. An aqueous polymer latex of a film-forming copolymer, which can be obtained by aqueous emulsion polymerization of an ethylenically unsaturated monomer M, wherein the ethylenically unsaturated monomer M comprises: - 20 to 90% by weight, based on the total amount of the monomers M, of at least one monomer M1 selected from isobutyl acrylate, 2-methylbutyl acrylate and isoamyl acrylate and mixtures thereof; - based on the total amount of the monomers M, 0 to 55 wt. % of at least one monomer M2 selected from the group consisting of ethyl acrylate, n-propyl acrylate, n-butyl acrylate, n-pentyl acrylate, C6-C 20 -alkyl esters and C5-C 20 - alkyl esters and mixtures thereof; - 5 to 50% by weight, based on the total amount of the monomers M, of at least one monomer M3 selected from the group consisting of tert-butyl acrylate, C1-C4-alkyl methacrylate, C5-C 20 -Cycloalkyl esters, C5-C 20 -Cycloalkyl esters, acrylic acid C5-C 20 -Cycloalkyl methyl ester, C5-C 20 - cycloalkyl methyl esters and monovinyl aromatic monomers and mixtures thereof, wherein in the above monomers the cycloalkyl group is monocyclic, bicyclic or tricyclic and wherein 1 or 2 non-adjacent CH2 moieties of the cycloalkyl group may be replaced by oxygen atoms and wherein the cycloalkyl group may be unsubstituted or carry 1, 2, 3 or 4 methyl groups, wherein the monomer M3 comprises methyl methacrylate; - 0.05 to 4% by weight, based on the total amount of the monomers M, of at least one monomer M4 selected from monoethylenically unsaturated monomers having an acidic group; The total amount of the monomers M1 and M2 is in the range of 45 to 94.95 wt % based on the total amount of the ethylenically unsaturated monomers M, and the total amount of the monomers M1, M2 and M3 is at least 90 wt % based on the total amount of the ethylenically unsaturated monomers M, wherein the particles of the copolymer contained in the polymer latex have a Z average particle size in the range of 40 to 350 nm as measured by quasi-elastic light scattering. 2 . The aqueous polymer latex of claim 1 , wherein the monomer M1 is isobutyl acrylate. 3 . The aqueous polymer latex of claim 1 , wherein the monomer M1 is isoamyl acrylate or a mixture comprising isoamyl acrylate and 2-methylbutyl acrylate in an amount of at least 80% based on the total amount of the monomer M1. 4 . The aqueous polymer latex according to claim 1 , wherein at least the carbon atoms of the isobutyl group, the 2-methylbutyl group and the isopentyl group in the monomer M1 are of bio-origin.

5. The aqueous polymer latex of any one of claims 1 to 3, wherein the monomer M2 is selected from n-butyl acrylate and 2-ethylhexyl acrylate and mixtures thereof.

6. The aqueous polymer latex of claim 1, wherein the monomer M3 is selected from methyl methacrylate and a combination of methyl methacrylate and at least one other monomer selected from tert-butyl acrylate, n-butyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate and styrene.

7. The aqueous polymer latex of any one of claims 1 to 3, wherein the monomer M4 is selected from acrylic acid, methacrylic acid, itaconic acid, and combinations thereof.

8. The aqueous polymer latex of any one of claims 1 to 3, wherein the monomers M further comprise at least one monoethylenically unsaturated, nonionic monomer M5 having a solubility in deionized water at 20°C and 1 bar of at least 60 g / L.

9. The aqueous polymer latex of claim 8, wherein the monomer M5 is selected from nonionic monoethylenically unsaturated monomers having a functional group selected from hydroxyalkyl, primary carboxamide, urea and keto groups and combinations thereof.

10. The aqueous polymer latex of any one of claims 1 to 3, wherein the monomer M consists of: i. 25 to 90% by weight of isobutyl acrylate as monomer M1, based on the total amount of the monomers M; ii. based on the total amount of the monomers M, 0 to 50 wt% of at least one monomer M2, the monomer M2 being selected from ethyl acrylate, n-propyl acrylate, n-butyl acrylate, C5-C 20 -alkyl esters and C5-C 20 - alkyl esters; iii. 10 to 45% by weight, based on the total amount of the monomers M, of at least one monomer M3 selected from the group consisting of tert-butyl acrylate, C1-C4-alkyl esters of methacrylic acid, C5-C 20 -Cycloalkyl esters, C5-C 20 -Cycloalkyl esters, acrylic acid C5-C 20 -Cycloalkyl methyl ester, C5-C 20 - cycloalkyl methyl esters and monovinyl aromatic monomers, wherein in the above monomers the cycloalkyl group is monocyclic, bicyclic or tricyclic, and wherein 1 or 2 non-adjacent CH2 moieties of the cycloalkyl group may be replaced by oxygen atoms, and wherein the cycloalkyl group may be unsubstituted or carry 1, 2, 3 or 4 methyl groups, wherein the monomer M3 comprises methyl methacrylate; iv. 0.05 to 4% by weight, based on the total amount of the monomers M, of one or more monoethylenically unsaturated monomers M4; v. 0 to 9.95% by weight, based on the total weight of the monomers M, of one or more nonionic monomers M5.

11. The aqueous polymer latex of any one of claims 1 to 3, wherein the monomer M comprises or consists of: i. 50 to 70% by weight of isobutyl acrylate as monomer M1, based on the total amount of the monomers M; iii. 30 to 50% by weight of methyl methacrylate as monomer M3, based on the total amount of the monomer M; iv. 0.1 to 4% by weight of a monoethylenically unsaturated carboxylic acid as monomer M4, based on the total amount of the monomers M; v. 0 to 5% by weight of monoethylenically unsaturated carboxylic acid amide as monomer M5a, based on the total amount of the monomers M; vi. 0 to 10% by weight, based on the total weight of the monomers M, of one or more ethylenically unsaturated nonionic monomers different from the monomers M1, M3, M4 and M5a.

12. The aqueous polymer latex of any one of claims 1 to 3, wherein the polymer particles comprise a polymer phase having a glass transition temperature Tg in the range of -25 to +40°C.

13. The aqueous polymer latex of any one of claims 1 to 3, wherein the polymer particles comprise a polymer phase (1) and a polymer phase (2), wherein the polymer phase (1) has a glass transition temperature Tg(1) in the range of -25 to +40°C, and the polymer phase (2) has a glass transition temperature Tg(2) in the range of +50 to +150°C.

14. The aqueous polymer latex according to claim 13, wherein at least 75% by weight of the monomers M1, based on the total amount of the monomers M1 present in the monomers M, is present in the polymer phase (1).

15. A process for preparing an aqueous polymer latex as claimed in any one of the preceding claims, said process comprising carrying out an aqueous emulsion polymerization of said monomer M.

16. The process of claim 15, wherein the aqueous emulsion polymerization is carried out by a monomer feeding method in which at least 90% of the monomers M to be polymerized are fed into a polymerization vessel as an aqueous emulsion of the monomers.

17. Use of the aqueous polymer latex according to any one of claims 1 to 14 as a binder in an aqueous coating composition.

18. An aqueous coating composition comprising: a) a binder polymer in the form of an aqueous polymer latex as claimed in any one of claims 1 to 14; b) at least one other ingredient used in aqueous coating compositions which is not a binder.

19. The water-based coating composition of claim 18, wherein the water-based coating composition is a latex paint.

20. The waterborne coating composition of claim 18, which is a latex paint for architectural coatings, wood coatings or wood staining compositions or a latex paint for interior coatings.

21. The aqueous coating composition according to any one of claims 18 to 20, comprising a titanium dioxide pigment.

22. The aqueous coating composition of claim 21, wherein a weight ratio of the polymer of the polymer latex to the titanium dioxide pigment is in the range of 0.1:5.0 to 5.0:0.

1.

23. Use of the aqueous polymer latex according to any one of claims 1 to 14 for improving the water resistance or moisture resistance of a coating obtained from an aqueous coating composition, or for improving the flexibility of a coating obtained from an aqueous coating composition.

Citation Information

Patent Citations

  • thickener for polyurethane base

    DE102004008015A1

  • polyurethane-based thickener

    DE102004031786A1

  • Process for the production of acrylic acid purified by crystallization from hydroxypropionic acid and apparatus therefor

    DE102006039203A1

  • Continuous removal of monomer from aqueous suspension or dispersion

    DE19621027A1

  • Removal of malodorous organic cpds. from dispersion

    DE19624299A1